Sex and base excision repair as key susceptibility factors for alkylation-induced mutations, toxicity and hepatic cancer - Jennifer E. Kay; Joshua J. Corrigan; Lindsay B. Volk; Amanda L. Armijo; Norah A. Owiti; Lee J. Pribyl; Ilana S. Nazari; Dorothea K. Torous; Svetlana L. Avlasevich; Robert G. Croy; Dushan N. Wadduwage; Sebastian E. Carrasco; et al. (DNA Repair, 2026)

Engaging European local communities in biodiversity genomics research: A five-step framework for scientists - Christian de Guttry; Chiara Bortoluzzi; Luísa S. Marins; Tinatin Chkhartishvili; Camilla R. De Pierri; Stefaniya Kamenova; Jennifer A. Leonard; Kay Lucek; Lada Lukić Bilela; Camila J. Mazzoni; Ann M. Mc Cartney; Svein-Ole Mikalsen; et al. (Biological Conservation, 2026)

Plastic extraction from dryer lint (PEDL): a low-tech, mass-based approach to quantify plastic microfibers in complex dryer lint - James Farnan; MC Cicenia; Troy Langknecht; Sarah M. Davis; Dounia Elkhatib; Robert M. Burgess; Kay T. Ho (Environmental Science and Pollution Research, 2026)

Associations of cardiorespiratory fitness with structural brain networks in ageing: insights from The Maastricht Study - Kristina Ukropcova; Kay Deckers; Annemarie Koster; Joost J. A. de Jong; Jacobus F. A. Jansen; Walter H. Backes; Hans H. C. M. Savelberg; Carla van der Kallen; Miranda T. Schram; Sebastian Köhler; Veerle van Gils (GeroScience, 2026)

The effects of simultaneous isometric and eccentric- or concentric-biased exercise on cardiovascular and muscular health of young individuals - A. W. Baross; B. H. Wright; D. A. Langdon; A. D. Kay; M. Cauchi; A. Clarke; B. Pitham; C. Willmont; T. Barnett; C. Key; M. Reynolds; A. Thomas; et al. (European Journal of Applied Physiology, 2026)

Using reflectance to measure chlorophyll a in corals: calibration and implications of skeletal optical properties - Kay Watty; Verena Schoepf; Kelly W. Johnson; Sophie Littke; Rene M. van der Zande (Coral Reefs, 2026)
Climate change-driven coral bleaching and associated chlorophyll (Chl) loss increasingly threaten coral reefs, highlighting the need for non-invasive, cost-effective tools to assess corals’ physiological condition. Researchers have explored the reflectance-based Normalized Difference Vegetation Index (NDVI) as a proxy for Chl a . However, almost no calibration curves exist to date; thus it remains unknown if the relationship between Chl a and NDVI differs among coral species, and whether it is influenced by skeletal optical properties. Here, we correlated Chl a content to NDVI in three coral species with different skeletal morphologies and reflectance modes across a range of health states (i.e., bleaching states). We found a strong positive relationship between Chl a and NDVI in all species, validating NDVI as a proxy for Chl a in corals. However, this relationship is non-linear, showing deviations at the highest and lowest ends of the pigmentation spectrum. We propose that in healthy states, this non-linearity is due to pigment self-shading, whereas in bleaching states, it is caused by backscattering of light by the increasingly exposed coral skeleton, because pigment loss enhances absorption by the remaining Chl a pigments and lowers, rather than increases, reflectance. To avoid Chl a under- or overestimation, we recommend to log-transform Chl a and create species-specific calibration curves. Overall, the non-invasive, repeatable, and scalable nature of reflectance measurements and NDVI make them valuable tools for assessing coral health both ex- and in situ. They provide a comprehensive view of the holobiont’s physiological condition and hold potential for broader applications in reef-scale monitoring, remote sensing, coral restoration, and conservation.

The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

The role of modifiable risk factors on the cerebral myelin content and cognition: findings from The Maastricht Study - Gerhard S. Drenthen; Walter H. Backes; Sebastian Köhler; Kay Deckers; Miranda T. Schram; Simone J. P. M. Eussen; Willemijn J. Jansen; Jacobus F. A. Jansen (GeroScience, 2026)
Lifestyle-related factors may affect cognition and increase the risk of developing dementia. However, the neurobiological mechanisms underlying the effect of lifestyle-related factors on the brain are not yet fully understood. Myelin, a vital element of brain health, has previously been shown to be involved in dementia-related cognitive decline. However, whether it plays a role in the relation between lifestyle-related factors and cognitive performance has not been studied. The cerebral myelin content of 4653 participants (51% female, aged 59 ± 9 years) from The Maastricht Study was estimated using the T1w/FLAIR-ratio, and lifestyle-related factors were summarized using the LIBRA-score. Multivariable linear regression models, corrected for the effects of age, sex and education, were used to investigate whether lifestyle-related factors are associated with myelin. Moreover, whether myelin can partly explain the relationship between lifestyle-related factors and cognition was explored using a mediation analysis across three cognitive domains (memory, executive functioning and processing speed). An unhealthy lifestyle (i.e. higher LIBRA score) is significantly associated to a lower cerebral myelin content ( β = −0.24, 95% CI [−0.26 −0.22], and p < 0.001). Furthermore, lower cerebral myelin content associates to worse cognitive performance ( β = 0.14, 95% CI [0.11 0.17], and p < 0.001). Moreover, myelin has a partially mediating effect of 15%, indicating that it partly explains the relation between lifestyle-related factors and cognition. These results show that myelin content might help explain the mechanisms through which lifestyle-related factors influence cognition, potentially allowing for specific and early lifestyle interventions aimed at preventing or delaying cognitive decline and dementia. Graphical abstract

Biodiversity Genomics Research Practices Require Harmonising to Meet Stakeholder Needs in Conservation - Elena Buzan; Christian de Guttry; Chiara Bortoluzzi; Nathaniel R. Street; Kay Lucek; Anna Rosling; Lino Ometto; Alice Mouton; Luísa S. Marins; María José Ruiz‐López; José Melo‐Ferreira; Elisabet Ottosson; et al. (Molecular Ecology, 2025)
Biodiversity resilience relies on genetic diversity, which sustains the evolutionary potential of organisms in dynamic ecosystems. Genomics is a powerful tool for accurately estimating genetic diversity across genomes of species and populations. However, integration of genomic data into conservation efforts faces challenges due to the heterogeneity of approaches employed. Establishing common sets of standards for genomic data production and analysis is essential to consistently interpret results and clearly communicate outcomes to stakeholders. While the European Reference Genome Atlas (ERGA) community has contributed significantly to the standardisation of reference genome methodologies in synergy with other initiatives, there is now an urgent need to extend these principles to downstream analyses. ERGA aims to build on its experience to help establish harmonised approaches in applied biodiversity genomics research, aligned with ongoing efforts to define standardised metrics for measuring and reporting genetic diversity. Establishing consensus on best practices for genome‐wide data generation methods and applications will substantially increase accuracy, interpretability, and comparability, together with enhanced stakeholder capacities. By identifying key opportunities and challenges, as well as conducting preliminary stakeholder mapping and examining case studies, the goal is to build an inclusive framework that ensures the relevance and widespread adoption of these best practices: fostering trust and confidence in genomics research practices to meet stakeholder needs in biodiversity conservation. We call upon the broader research community to join efforts in establishing these approaches, recognising the importance of participation of end‐users, to foster the integration of genomic data into the toolkit for measuring and reporting genetic diversity.

Workflow for the Creation of 3D Stereoscopic Models of Supra- and Infratentorial Brain Venous Anatomy and their Integration in a Virtual Reality Environment - Francesco Carbone; Toma Spiriev; Martin Trandzhiev; Michael Wolf-Vollenbröker; Kay M. Körner; Andrea Steuwe; Matteo de Notaris; Vladimir Nakov; Jan F. Cornelius (Neuroinformatics, 2025)

Current Views on Addressing Nutritional Concerns in Adult Cystic Fibrosis Patients from Practicing Registered Dietitians - C. West; M. Kay; P. Davidson; L. Wright; C. Colin (Journal of the Academy of Nutrition and Dietetics, 2025)

Retrofitted watershed scale green infrastructure reduces heavy metals in urban stormwater from residential land use - Joseph S. Smith; Kay Bernard; Kathryn M. Boening-Ulman; Jay F. Martin; R. Andrew Tirpak; David M. Wituszynski; Ryan J. Winston (Journal of Hazardous Materials, 2025)

Novel Correlations Between Lung Function and Gut Microbial-Produced VOCs in the Exhaled Breath of Ultramarathon Runners: Insights from the 2019 Ultra-Trail du Mont Blanc - Hsuan Chou; Amy Craster; Kayleigh Arthur; Billy Boyle; Max Allsworth; Eli F. Kelley; Glenn M. Stewart; Courtney M. Wheatley-Guy; Jesse Schwartz; Caitlin C. Fermoyle; Briana L. Ziegler; Kay A. Johnson; et al. (Journal of Science in Sport and Exercise, 2025)

Marine data assimilation in the UK: the past, the present, and the vision for the future - Jozef Skákala; David Ford; Keith Haines; Amos Lawless; Matthew J. Martin; Philip Browne; Marcin Chrust; Stefano Ciavatta; Alison Fowler; Daniel Lea; Matthew Palmer; Andrea Rochner; et al. (Ocean Science, 2025)
In the last 2 decades, UK research institutes have led a wide range of developments in marine data assimilation (MDA), covering areas from operational applications in physics and biogeochemistry to fundamental theory. We highlight the emergence of strong collaboration in the UK MDA community over this period and the increasing unification of its tools. We focus on identifying the MDA stakeholder community and current/future areas of impact, as well as current trends and future opportunities. This includes the rapid growth of machine learning (ML)/artificial intelligence (AI) and digital-twin applications. We articulate a vision for the future, including the need for future types of observational data (whether planned missions or hypothetical) and how the community should respond to increases in computational power and new computer architectures (e.g. exascale computing). We contrast the requirements of different MDA areas, including physics, biogeochemistry, and coupled data assimilation (DA). Although the specifics of the vision depend on each area, common themes emerge. We advocate for balanced redistribution of new computational capability among increased model resolution, model complexity, more sophisticated DA algorithms, and uncertainty representation (e.g. ensembles). We also advocate for integrated approaches, such as strongly coupled DA (ocean–atmosphere, physics–biogeochemistry, and ocean–sea ice) and the use of ML/AI components (e.g. for multivariate increment balancing, bias correction, model emulation, observation re-gridding, or fusion).

Toxicological impacts of plastic microfibers from face masks on Artemia salina: An environmental assessment using Box-Behnken design - Devlina Das Pramanik; Armeena Sharma; Deepak Kumar Das; Arindam Pramanik; Paul Kay; Francisco M. Goycoolea (Marine Environmental Research, 2024)

Age-dependent somatic expansion of the ATXN3 CAG repeat in the blood and buccal swab DNA of individuals with spinocerebellar ataxia type 3/Machado-Joseph disease - Ahmed M. Sidky; Ana Rosa Vieira Melo; Teresa T. Kay; Mafalda Raposo; Manuela Lima; Darren G. Monckton (Human Genetics, 2024)
Spinocerebellar ataxia type 3/Machado-Joseph disease (SCA3/MJD) is caused by the expansion of a genetically unstable polyglutamine-encoding CAG repeat in ATXN3 . Longer alleles are generally associated with earlier onset and frequent intergenerational expansions mediate the anticipation observed in this disorder. Somatic expansion of the repeat has also been implicated in disease onset and slowing the rate of somatic expansion has been proposed as a therapeutic strategy. Here, we utilised high-throughput ultra-deep MiSeq amplicon sequencing to precisely define the number and sequence of the ATXN3 repeat, the genotype of an adjacent single nucleotide variant and quantify somatic expansion in blood and buccal swab DNA of a cohort of individuals with SCA3 from the Azores islands (Portugal). We revealed systematic mis-sizing of the ATXN3 repeat and high levels of inaccuracy of the traditional fragment length analysis that have important implications for attempts to identify modifiers of clinical and molecular phenotypes. Quantification of somatic expansion in blood DNA and multivariate regression revealed the expected effects of age at sampling and CAG repeat length, although the effect of repeat length was surprisingly modest with much stronger associations with age. We also observed an association of the downstream rs12895357 single nucleotide variant with the rate of somatic expansion, and a higher level of somatic expansion in buccal swab DNA compared to blood. These data suggest that the ATXN3 locus in SCA3 patients in blood or buccal swab DNA might serve as a good biomarker for clinical trials testing suppressors of somatic expansion with peripheral exposure.

Comparing the definitions of microplastics based on size range: Scientific and policy implications - Kay T. Ho; Rhema Bjorkland; Robert M. Burgess (Marine Pollution Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Lower crustal control in the iron isotope systematics of plutonic xenoliths from Adak Island, Central Aleutians, with implications for arc magma geochemistry - Emma S. Sosa; Claire E. Bucholz; Juan David Hernández-Montenegro; Michael A. Kipp; François L.H. Tissot; Barbara C. Ratschbacher; Jennifer M. Jackson; Suzanne Mahlburg Kay; Robert W. Kay (Geochimica et Cosmochimica Acta, 2024)

A multispecies hierarchical model to integrate count and distance‐sampling data - Neil A. Gilbert; Caroline M. Blommel; Matthew T. Farr; David S. Green; Kay E. Holekamp; Elise F. Zipkin (Ecology, 2024)
Integrated community models—an emerging framework in which multiple data sources for multiple species are analyzed simultaneously—offer opportunities to expand inferences beyond the single‐species and single‐data‐source approaches common in ecology. We developed a novel integrated community model that combines distance sampling and single‐visit count data; within the model, information is shared among data sources (via a joint likelihood) and species (via a random‐effects structure) to estimate abundance patterns across a community. Parameters relating to abundance are shared between data sources, and the model can specify either shared or separate observation processes for each data source. Simulations demonstrated that the model provided unbiased estimates of abundance and detection parameters even when detection probabilities varied between the data types. The integrated community model also provided more accurate and more precise parameter estimates than alternative single‐species and single‐data‐source models in many instances. We applied the model to a community of 11 herbivore species in the Masai Mara National Reserve, Kenya, and found considerable interspecific variation in response to local wildlife management practices: Five species showed higher abundances in a region with passive conservation enforcement (median across species: 4.5× higher), three species showed higher abundances in a region with active conservation enforcement (median: 3.9× higher), and the remaining three species showed no abundance differences between the two regions. Furthermore, the community average of abundance was slightly higher in the region with active conservation enforcement but not definitively so (posterior mean: higher by 0.20 animals; 95% credible interval: 1.43 fewer animals, 1.86 more animals). Our integrated community modeling framework has the potential to expand the scope of inference over space, time, and levels of biological organization, but practitioners should carefully evaluate whether model assumptions are met in their systems and whether data integration is valuable for their applications.

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

CometChip enables parallel analysis of multiple DNA repair activities [DNA repair 106 (2021) 103176–103202] - Jing Ge; Le P. Ngo; Simran Kaushal; Ian J. Tay; Elina Thadhani; Jennifer E. Kay; Patrizia Mazzucato; Danielle Chow; Jessica Fessler; David M. Weingeist; Robert W. Sobol; Leona D. Samson; et al. (DNA Repair, 2024)

The distribution of sediment microplastics assemblages is driven by location and hydrodynamics, not sediment characteristics, in the Gulf of Maine, USA - Troy Langknecht; Marguerite Pelletier; Sandra Robinson; Robert M. Burgess; Kay T. Ho (Marine Pollution Bulletin, 2024)

Concordance in dietary intake among caregivers and infants during the period of complementary feeding: A scoping review - Sara V. Bernate Angulo; Brooke T. Nezami; Stephanie L. Martin; Melissa C. Kay; Taylor N. Richardson; Heather M. Wasser (Appetite, 2024)

Incorporating climate-readiness into fisheries management strategies - Elizabeth Talbot; Jean-Beth S. Jontila; Benjamin J. Gonzales; Roger G. Dolorosa; Edgar D. Jose; Recca Sajorne; Sevrine Sailley; Susan Kay; Ana M. Queirós (Science of The Total Environment, 2024)

A rapid and portable fluorescence spectroscopy staining method for the detection of plastic microfibers in water - Devlina Das Pramanik; Paul Kay; Francisco M. Goycoolea (Science of The Total Environment, 2024)

The multiview observatory for solar terrestrial science (MOST) - N. Gopalswamy; S. Christe; S.F. Fung; Q. Gong; J.R. Gruesbeck; L.K. Jian; S.G. Kanekal; C. Kay; T.A. Kucera; J.E. Leake; L. Li; P. Mӓkelӓ; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Observing Antarctic Bottom Water in the Southern Ocean - Alessandro Silvano; Sarah Purkey; Arnold L. Gordon; Pasquale Castagno; Andrew L. Stewart; Stephen R. Rintoul; Annie Foppert; Kathryn L. Gunn; Laura Herraiz-Borreguero; Shigeru Aoki; Yoshihiro Nakayama; Alberto C. Naveira Garabato; et al. (Frontiers in Marine Science, 2023)
Dense, cold waters formed on Antarctic continental shelves descend along the Antarctic continental margin, where they mix with other Southern Ocean waters to form Antarctic Bottom Water (AABW). AABW then spreads into the deepest parts of all major ocean basins, isolating heat and carbon from the atmosphere for centuries. Despite AABW’s key role in regulating Earth’s climate on long time scales and in recording Southern Ocean conditions, AABW remains poorly observed. This lack of observational data is mostly due to two factors. First, AABW originates on the Antarctic continental shelf and slope where in situ measurements are limited and ocean observations by satellites are hampered by persistent sea ice cover and long periods of darkness in winter. Second, north of the Antarctic continental slope, AABW is found below approximately 2 km depth, where in situ observations are also scarce and satellites cannot provide direct measurements. Here, we review progress made during the past decades in observing AABW. We describe 1) long-term monitoring obtained by moorings, by ship-based surveys, and beneath ice shelves through bore holes; 2) the recent development of autonomous observing tools in coastal Antarctic and deep ocean systems; and 3) alternative approaches including data assimilation models and satellite-derived proxies. The variety of approaches is beginning to transform our understanding of AABW, including its formation processes, temporal variability, and contribution to the lower limb of the global ocean meridional overturning circulation. In particular, these observations highlight the key role played by winds, sea ice, and the Antarctic Ice Sheet in AABW-related processes. We conclude by discussing future avenues for observing and understanding AABW, impressing the need for a sustained and coordinated observing system.

Planning precision aquaculture activities in a changing and crowded sea - M. Cristina Mangano; Laura Corbari; Antonio Giacoletti; Manuel Berlino; Susan Kay; Giuseppe Ciraolo; Gianluca Sarà (Aquaculture, 2023)

Using eRNA/eDNA metabarcoding to detect community-level impacts of nanoplastic exposure to benthic estuarine ecosystems - Marissa S. Giroux; Jay R. Reichman; Troy Langknecht; Robert M. Burgess; Kay T. Ho (Environmental Pollution, 2023)

Quantifying errors in 3D CME parameters derived from synthetic data using white-light reconstruction techniques - Christine Verbeke; M. Leila Mays; Christina Kay; Pete Riley; Erika Palmerio; Mateja Dumbović; Marilena Mierla; Camilla Scolini; Manuela Temmer; Evangelos Paouris; Laura A. Balmaceda; Hebe Cremades; et al. (Advances in Space Research, 2023)

Corrigendum to “Quantification of microplastics in sediments from Narragansett Bay, Rhode Island USA using a novel isolation and extraction method” [Mar. Pollut. Bull. 174 (2022) 113254] - Michaela Cashman; Troy Langknecht; Dounia El Khatib; Robert M. Burgess; Thomas B. Boving; Sandra Robinson; James Farnan; Kay T. Ho (Marine Pollution Bulletin, 2023)

Ambient air particulate total lung deposited surface area (LDSA) levels in urban Europe - Xiansheng Liu; Hadiatullah Hadiatullah; Xun Zhang; Pedro Trechera; Marjan Savadkoohi; Meritxell Garcia-Marlès; Cristina Reche; Noemí Pérez; David C.S. Beddows; Imre Salma; Wanda Thén; Panayiotis Kalkavouras; et al. (Science of The Total Environment, 2023)

Wild lime psyllid Leuronota fagarae Burckhardt (Hemiptera: Psylloidea) picorna-like virus full genome annotation and classification - Douglas S. Stuehler; Wayne B. Hunter; Yisel Carrillo-Tarazona; Hector Espitia; Joseph M. Cicero; Tracey Bell; Hannah R. Mann; Sasha-Kay V. Clarke; Thomson M. Paris; Jackie L. Metz; Tom D'Elia; Jawwad A. Qureshi; et al. (Journal of Invertebrate Pathology, 2023)

The influence of complex matrices on method performance in extracting and monitoring for microplastics - Leah M. Thornton Hampton; Hannah De Frond; Kristine Gesulga; Syd Kotar; Wenjian Lao; Cindy Matuch; Stephen B. Weisberg; Charles S. Wong; Susanne Brander; Silke Christansen; Cayla R. Cook; Fangni Du; et al. (Chemosphere, 2023)

Mixtures of sediment chemical contaminants at freshwater sampling sites across Europe with different contaminant burdens - Samantha Richardson; Will M. Mayes; Sonja Faetsch; Hanne Hetjens; Johnny Teuchies; Paul Walker; Katharina Heitmann; Kevin Welham; Dean Moore; Lieven Bervoets; Paul Kay; Wayne Duffus; et al. (Science of The Total Environment, 2023)

PK/PD and Bioanalytical Considerations of AAV-Based Gene Therapies: an IQ Consortium Industry Position Paper - Uma Kavita; Kefeng Sun; Manuela Braun; Wibke Lembke; Hardik Mody; John Kamerud; Tong-Yuan Yang; Inka V. Braun; Xiaodong Fang; Wei Gao; Swati Gupta; Magdalena Hofer; et al. (The AAPS Journal, 2023)

Assessment of filter subsampling and extrapolation for quantifying microplastics in environmental samples using Raman spectroscopy - Dounia El Khatib; Troy D. Langknecht; Michaela A. Cashman; Mark Reiss; Kelly Somers; Harry Allen; Kay T. Ho; Robert M. Burgess (Marine Pollution Bulletin, 2023)

Investigating on the toxicity and bio-magnification potential of synthetic glitters on Artemia salina - Devlina Das Pramanik; Sihan Lei; Paul Kay; Francisco M. Goycoolea (Marine Pollution Bulletin, 2023)

Quantification of groundwater discharge into a shallow coastal lagoon applying a multi-tracer approach - Michael Schubert; Kay Knoeller; Jan Scholten; L. Walter Daesslé; Mauricio M. Reyes Bravo; Efraín M. Chávez Solís (Environmental Monitoring and Assessment, 2023)
In many cases, shallow coastal lagoons are, on the one hand, vulnerable habitats for birds and marine ecosystems and, on the other hand, threatened by discharging nutrient-laden surface waters and groundwater. In particular, the localization and quantification of submarine groundwater discharge (SGD) is of key concern in this regard. The presented study aimed at investigating SGD into a vulnerable coastal lagoon that is strongly impacted by evaporation applying a multi-tracer approach. The joint application of radionuclides ( 222 Rn, 223 Ra, 224 Ra), stable water isotopes (δ 18 O, δ 2 H) and the water salinity as environmental water tracers allowed evaluating the suitability of the individual parameters in this specific type of environment. Whilst stable isotope and salinity data were difficult to construe in terms of SGD occurrence due to the intense impact of evaporation, a radon mass balance allowed localising SGD areas within the lagoon and quantifying the related SGD flux rates. In addition, a 224 Ra/ 223 Ra ratio analysis revealed information on the apparent age of the discharged groundwater, and hence on the flushing intensity of the lagoon. Besides these site-specific results, the study allowed the following general conclusions regarding the suitability of the applied tracers: (i) we verified the suitability of a radon mass balance approach for proving/disproving SGD occurrence and quantifying SGD fluxes in shallow coastal lagoons strongly impacted by evaporation; (ii) we showed that the impact of evaporation may impede the use of water stable isotope and salinity data as SGD indicators in such specific environments; (iii) we demonstrated that the tidal impact on a lagoon water body during a sampling campaign can be compensated by adapting sampling schedule and cruise track to the tidal cycle.

Photometry of LROC NAC resolved rock-rich regions on the Moon - Rachael M. Marshal; Ottaviano Rüsch; Christian Wöhler; Kay Wohlfarth; Sergey Velichko (Icarus, 2023)

Projected effects of climate change on marine ecosystems in Southeast Asian seas - Susan Kay; Arlene L. Avillanosa; Victoria V. Cheung; Hung N. Dao; Benjamin Jareta Gonzales; Herminie P. Palla; Radisti A. Praptiwi; Ana M. Queirós; Sévrine F. Sailley; Joel D. C. Sumeldan; Wan Mohd Syazwan; Amy Yee-Hui Then; et al. (Frontiers in Marine Science, 2023)
The seas of Southeast Asia are home to some of the world’s most diverse ecosystems and resources that support the livelihoods of millions of people. Climate change will bring temperature changes, acidification and other environmental change, with uncertain consequences for human and natural systems, but there has been little regional-scale climate modelling of the marine ecosystem. We present initial dynamically downscaled projections using a biogeochemical model suitable for coastal and shelf seas. A coupled physical-biogeochemical model with a resolution of 0.1° (approximately 11 km) was used to create projections of future environmental conditions under moderate (RCP4.5) and high (RCP8.5) greenhouse gas scenarios. Changes for different parts of the region are presented, including four sensitive coastal sites of key importance for biodiversity and sustainable development: UNESCO Biosphere Reserves at Cu Lao Cham-Hoi An in Vietnam, Palawan in the Philippines and Taka Bonerate-Kepulauan Selayar in Indonesia, and coastal waters of Sabah, Malaysia, which include several marine parks. The projections show a sea that is warming by 1.1 to 2.9°C through the 21st century, with dissolved oxygen decreasing by 5 to 13 mmol m -3 and changes in many other environmental variables. The changes reach all parts of the water column and many places are projected to experience conditions well outside the range seen at the start of the century. The resulting damage to coral reefs and altered species distribution would have consequences for biodiversity, the livelihoods of small-scale fishers and the food security of coastal communities. Further work using a range of global models and regional models with different biogeochemical components is needed to provide confidence levels, and we suggest some ways forward. Projections of this type serve as a key tool for communities and policymakers as they plan how they will adapt to the challenge of climate change.

Thalamus sends information about arousal but not valence to the amygdala - Chris A. Leppla; Laurel R. Keyes; Gordon Glober; Gillian A. Matthews; Kanha Batra; Maya Jay; Yu Feng; Hannah S. Chen; Fergil Mills; Jeremy Delahanty; Jacob M. Olson; Edward H. Nieh; et al. (Psychopharmacology, 2023)
Rationale The basolateral amygdala (BLA) and medial geniculate nucleus of the thalamus (MGN) have both been shown to be necessary for the formation of associative learning. While the role that the BLA plays in this process has long been emphasized, the MGN has been less well-studied and surrounded by debate regarding whether the relay of sensory information is active or passive. Objectives We seek to understand the role the MGN has within the thalamoamgydala circuit in the formation of associative learning. Methods Here, we use optogenetics and in vivo electrophysiological recordings to dissect the MGN-BLA circuit and explore the specific subpopulations for evidence of learning and synthesis of information that could impact downstream BLA encoding. We employ various machine learning techniques to investigate function within neural subpopulations. We introduce a novel method to investigate tonic changes across trial-by-trial structure, which offers an alternative approach to traditional trial-averaging techniques. Results We find that the MGN appears to encode arousal but not valence, unlike the BLA which encodes for both. We find that the MGN and the BLA appear to react differently to expected and unexpected outcomes; the BLA biased responses toward reward prediction error and the MGN focused on anticipated punishment. We uncover evidence of tonic changes by visualizing changes across trials during inter-trial intervals (baseline epochs) for a subset of cells. Conclusion We conclude that the MGN-BLA projector population acts as both filter and transferer of information by relaying information about the salience of cues to the amygdala, but these signals are not valence-specified.

Comparison of two procedures for microplastics analysis in sediments based on an interlaboratory exercise - Troy Langknecht; Wenjian Lao; Charles S. Wong; Syd Kotar; Dounia El Khatib; Sandra Robinson; Robert M. Burgess; Kay T. Ho (Chemosphere, 2023)

Intralesional application of ribavirin in two American flamingos (Phoenicopterus ruber) with poxvirus infection - Giuseppe M Marcello; Kali A Holder; Sara Hallager; Benjamin B Norton; Kay A Backues; Anna E Tyler; Ayo Zeitlin; Evan Murray-Hiteshew; Suzan Murray (Journal of Comparative Pathology, 2023)

High-performance post-treatment-free PEDOT based thermoelectric with the establishment of long-range ordered conductive paths - Xin Li; Zhenhang He; Zhen Liu; Yu Chen; Zekun Zhou; Guixiang Chen; Weiheng Qi; Daniel Rauber; Christopher W. M. Kay; Peng Zhang (Chemical Engineering Journal, 2023)

Combined effects of increased water temperature and cyanobacterial compounds exert heterogeneous effects on survival and ecological processes in key freshwater species - Oloyede A. Adekolurejo; Matthew Floyd; Alison M. Dunn; Paul Kay; Andrew P. Dean; Christopher Hassall (Oecologia, 2022)
Climate change is increasing water temperature and intensifying the incidence of cyanobacterial blooms worldwide. However, the combined effects of increased temperature and microcystin concentrations as co-stressors on survival and ecological processes in freshwater species are unclear. Here, using purified MC-LR and crude extract of toxigenic Microcystis aeruginosa , we tested the individual and combined effects of three water temperatures (15, 20, 25 °C) and a range of environmentally relevant concentrations of dissolved microcystin and crude extract (0.01–10 µg·L −1 ) on survival, growth inhibition, grazing and predation rates in three freshwater species: phytoplankton ( Scenedesmus quadricauda ), zooplankton ( Daphnia pulex ), and an invertebrate predator ( Ischnura elegans ). Purified MC-LR exerted a higher growth inhibitory effect on S. quadricauda compared to crude extract with the same concentration of MC-LR, while neither treatment affected its chlorophyll-a content or survival of D. pulex . Crude extract reduced grazing and survival of D. pulex and I. elegans , respectively. The combined effect of higher temperature and crude extract reduced I. elegans survival by 50% . Increased temperature reduced prey handing time in I. elegans by 49%, suggesting a higher predation rate. However, warming together with higher concentrations of crude extract jointly increased zooplankton grazing and reduced damselfly predation. Taken together, these results suggest crude extract, and not necessarily microcystin, can affect survival and productivity in freshwater species, although these effects may vary unevenly across trophic levels. Our findings highlight the importance of complex ecological mechanisms by which warming can exacerbate toxic effects of cyanobacterial bloom extracts on survival and functions among species in eutrophic freshwaters.

Sign-oriented Dirichlet Normal Energy: Aligning Dental Topography and Dental Function in the R-package molaR - James D. Pampush; Paul E. Morse; Edward J. Fuselier; Matthew M. Skinner; Richard F. Kay (Journal of Mammalian Evolution, 2022)

EGR3 regulates opioid-related nociception and motivation in male rats - Swarup Mitra; Shruthi A. Thomas; Jennifer A. Martin; Jamal Williams; Kristen Woodhouse; Ramesh Chandra; Jun Xu Li; Mary Kay Lobo; Fraser J. Sim; David M. Dietz (Psychopharmacology, 2022)

A globally relevant change taxonomy and evidence‐based change framework for land monitoring - Richard M. Lucas; Sophia German; Graciela Metternicht; Rebecca K. Schmidt; Christopher J. Owers; Suzanne M. Prober; Anna E. Richards; Sally Tetreault‐Campbell; Kristen J. Williams; Norman Mueller; Belle Tissott; Sean M. T. Chua; et al. (Global Change Biology, 2022)
A globally relevant and standardized taxonomy and framework for consistently describing land cover change based on evidence is presented, which makes use of structured land cover taxonomies and is underpinned by the Driver‐Pressure‐State‐Impact‐Response (DPSIR) framework. The Global Change Taxonomy currently lists 246 classes based on the notation ‘impact (pressure)’, with this encompassing the consequence of observed change and associated reason(s), and uses scale‐independent terms that factor in time. Evidence for different impacts is gathered through temporal comparison (e.g., days, decades apart) of land cover classes constructed and described from Environmental Descriptors (EDs; state indicators) with pre‐defined measurement units (e.g., m, %) or categories (e.g., species type). Evidence for pressures, whether abiotic, biotic or human‐influenced, is similarly accumulated, but EDs often differ from those used to determine impacts. Each impact and pressure term is defined separately, allowing flexible combination into ‘impact (pressure)’ categories, and all are listed in an openly accessible glossary to ensure consistent use and common understanding. The taxonomy and framework are globally relevant and can reference EDs quantified on the ground, retrieved/classified remotely (from ground‐based, airborne or spaceborne sensors) or predicted through modelling. By providing capacity to more consistently describe change processes—including land degradation, desertification and ecosystem restoration—the overall framework addresses a wide and diverse range of local to international needs including those relevant to policy, socioeconomics and land management. Actions in response to impacts and pressures and monitoring towards targets are also supported to assist future planning, including impact mitigation actions.

Chemical Effects on Breast Development, Function, and Cancer Risk: Existing Knowledge and New Opportunities - Jennifer E. Kay; Bethsaida Cardona; Ruthann A. Rudel; Laura N. Vandenberg; Ana M. Soto; Sofie Christiansen; Linda S. Birnbaum; Suzanne E. Fenton (Current Environmental Health Reports, 2022)
Population studies show worrisome trends towards earlier breast development, difficulty in breastfeeding, and increasing rates of breast cancer in young women. Multiple epidemiological studies have linked these outcomes with chemical exposures, and experimental studies have shown that many of these chemicals generate similar effects in rodents, often by disrupting hormonal regulation. These endocrine-disrupting chemicals (EDCs) can alter the progression of mammary gland (MG) development, impair the ability to nourish offspring via lactation, increase mammary tissue density, and increase the propensity to develop cancer. However, current toxicological approaches to measuring the effects of chemical exposures on the MG are often inadequate to detect these effects, impairing our ability to identify exposures harmful to the breast and limiting opportunities for prevention. This paper describes key adverse outcomes for the MG, including impaired lactation, altered pubertal development, altered morphology (such as increased mammographic density), and cancer. It also summarizes evidence from humans and rodent models for exposures associated with these effects. We also review current toxicological practices for evaluating MG effects, highlight limitations of current methods, summarize debates related to how effects are interpreted in risk assessment, and make recommendations to strengthen assessment approaches. Increasing the rigor of MG assessment would improve our ability to identify chemicals of concern, regulate those chemicals based on their effects, and prevent exposures and associated adverse health effects.

The genetic basis of floral mechanical isolation between two hummingbird‐pollinated Neotropical understorey herbs - Kathleen M. Kay; Yann Surget‐Groba (Molecular Ecology, 2022)
Floral divergence can contribute to reproductive isolation among plant lineages, and thus provides an opportunity to study the genetics of speciation, including the number, effect size, mode of action and interactions of quantitative trait loci (QTL). Moreover, flowers represent suites of functionally interrelated traits, but it is unclear to what extent the phenotypic integration of the flower is underlain by a shared genetic architecture, which could facilitate or constrain correlated evolution of floral traits. Here, we examine the genetic architecture of floral morphological traits involved in an evolutionary switch from bill to forehead pollen placement between two species of hummingbird‐pollinated Neotropical understorey herbs that are reproductively isolated by these floral differences. For the majority of traits, we find multiple QTL of relatively small effect spread throughout the genome. We also find substantial colocalization and alignment of effects of QTL underlying different floral traits that function together to promote outcrossing and reduce heterospecific pollen transfer. Our results are consistent with adaptive pleiotropy or linkage of many co‐adapted genes, either of which could have facilitated a response to correlated selection and helped to stabilize divergent phenotypes in the face of low levels of hybridization. Moreover, our results indicate that floral mechanical isolation can be consistent with an infinitesimal model of adaptation.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Quantifying cancer risk from exposures to medical imaging in the Risk of Pediatric and Adolescent Cancer Associated with Medical Imaging (RIC) Study: research methods and cohort profile - Marilyn L. Kwan; Diana L. Miglioretti; Erin J. A. Bowles; Sheila Weinmann; Robert T. Greenlee; Natasha K. Stout; Alanna Kulchak Rahm; Susan A. Alber; Priscila Pequeno; Lisa M. Moy; Carly Stewart; Cindy Fong; et al. (Cancer Causes & Control, 2022)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

A pooled case-only analysis of obesity and breast cancer subtype among Black women in the southeastern United States - Jaleesa Moore; Tuya Pal; Alicia Beeghly-Fadiel; Mary Kay Fadden; Heather M. Munro; Steffie-Ann Dujon; Sonya Reid; Ann Tezak; Miaya Blasingame; Jeania Ware; William J. Blot; Xiao-Ou Shu; et al. (Cancer Causes & Control, 2022)

Plant community responses to experimental climate manipulation in a Welsh ombrotrophic peatland and their palaeoenvironmental context - Luke O. Andrews; James G. Rowson; Simon J. M. Caporn; Nancy B. Dise; Eleanor Barton; Ed Garrett; W. Roland Gehrels; Maria Gehrels; Martin Kay; Richard J. Payne (Global Change Biology, 2022)
We test whether vegetation community composition from a 10‐year climate manipulation experiment on a Welsh peat bog resembles vegetation communities during periods of climate change inferred from a peat core. Experimentally warmed and combined warmed and droughted treatments drove significant increases in ericaceous shrubs but Sphagnum was unaffected. Similarly, Calluna vulgaris seeds increase during inferred warmer periods in the palaeoecological record. Experimental short‐term episodic drought (four 4‐week drought treatments) did not affect vegetation. Plant community composition has undergone several abrupt changes throughout the past c. 1500 years, often in response to human disturbance. Only slight changes occurred during the Medieval Climate Anomaly (c. 950–1250 Common Era [CE]) in vegetation and hydrology, while abrupt changes occurred during the Little Ice Age (c. 1300–1850 CE) when water tables were highest, suggesting that these shifts were driven by changes in water table, modulated by climate. A period of water table drawdown c. 1800, synchronous with historical records of increased drainage, corresponds with the development of the present‐day vegetation community. Modern analogues for fossil material, characterized by abundant Rhynchospora alba and Sphagnum pulchrum , are more common after this event. Vegetation changes due to climate inferred from the palaeo record differ from those observed in the experiments, possibly relating to differences in the importance of drivers of vegetation change over varying timescales. Whereas temperature is frequently identified as the dominant driver of plant community change in experiments, sustained changes in water table appear to be more important in the long‐term record. We find evidence that recent climate change and other anthropogenic stressors (e.g. drainage, heavy metal and nitrogen pollution) may promote the development of novel plant communities without analogues in the fossil record. These communities may be poorer at sequestering carbon and may respond differently to future climate change.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Human cytomegalovirus multiple-strain infections and viral population diversity in haematopoietic stem cell transplant recipients analysed by high-throughput sequencing - A. Dhingra; J. Götting; P. R. Varanasi; L. Steinbrueck; S. Camiolo; J. Zischke; A. Heim; T. F. Schulz; E. M. Weissinger; P. C. Kay-Fedorov; A. J. Davison; N. M. Suárez; et al. (Medical Microbiology and Immunology, 2021)
Human cytomegalovirus (HCMV) is an important opportunistic pathogen in allogeneic haematopoietic stem cell transplant (HSCT) recipients. High-throughput sequencing of target-enriched libraries was performed to characterise the diversity of HCMV strains present in this high-risk group. Forty-four HCMV-DNA-positive plasma specimens (median viral input load 321 IU per library) collected at defined time points from 23 HSCT recipients within 80 days of transplantation were sequenced. The genotype distribution for 12 hypervariable HCMV genes and the number of HCMV strains present (i.e. single- vs. multiple-strain infection) were determined for 29 samples from 16 recipients. Multiple-strain infection was observed in seven of these 16 recipients, and five of these seven recipients had the donor (D)/recipient (R) HCMV-serostatus combination D + R + . A very broad range of genotypes was detected, with an intrahost composition that was generally stable over time. Multiple-strain infection was not associated with particular virological or clinical features, such as altered levels or duration of antigenaemia, development of acute graft-versus-host disease or increased mortality. In conclusion, despite relatively low viral plasma loads, a high frequency of multiple-strain HCMV infection and a high strain complexity were demonstrated in systematically collected clinical samples from this cohort early after HSCT. However, robust evaluation of the pathogenic role of intrahost viral diversity and multiple-strain infection will require studies enrolling larger numbers of recipients.

Effects of a physical activity intervention on brain atrophy in older adults at risk of dementia: a randomized controlled trial - Benjamin Sinclair; Chris Steward; Vijay Venkatraman; Rowa Aljondi; Kay L. Cox; Kathryn A. Ellis; David Ames; Colin L. Masters; Pramit M. Phal; Matthew J. Sharman; Elizabeth V. Cyarto; Michelle M. Y. Lai; et al. (Brain Imaging and Behavior, 2021)

The Uptake of Sporopollenin Exine Capsules and Associated Bioavailability of Adsorbed Oestradiol in Selected Aquatic Invertebrates - Emma Chapman; Aimilia Meichanetzoglou; Andrew N. Boa; Hanne Hetjens; Sonja Faetsch; Johnny Teuchies; Sebastian Höss; Dean Moore; Lieven Bervoets; Paul Kay; Susanne Heise; Paul Walker; et al. (Bulletin of Environmental Contamination and Toxicology, 2021)
Lycopodium clavatum sporopollenin exine capsules (SpECs) are known to both adsorb and absorb chemicals. The aim of the present work was to determine whether oestradiol (E2) is ‘bioavailable’ to bioindicator species, either pre-adsorbed to, or in the presence of, SpECs. SpEC uptake was confirmed for Daphnia magna and Dreissena bugensis . E2 levels varied among treatments for Caenorhabditis elegans though there was no relationship to SpEC load. E2 was not detected in D. bugensis tissues. Expression changes of general stress and E2-specific genes were measured. For C. elegans , NHR-14 expression suggested that SpECs modulate E2 impacts, but not general health responses. For D. magna , SpECs alone and with E2 changed Vtg1 and general stress responses. For D. bugensis , SpECS were taken up but no E2 or change in gene expression was detected after exposure to E2 and/or SpECs. The present study is the first to investigate SpECs and bound chemical dynamics.

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

Bright spots as climate‐smart marine spatial planning tools for conservation and blue growth - Ana M. Queirós; Elizabeth Talbot; Nicola J. Beaumont; Paul J. Somerfield; Susan Kay; Christine Pascoe; Simon Dedman; Jose A. Fernandes; Alexander Jueterbock; Peter I. Miller; Sevrine F. Sailley; Gianluca Sará; et al. (Global Change Biology, 2021)
Marine spatial planning that addresses ocean climate‐driven change (‘climate‐smart MSP’) is a global aspiration to support economic growth, food security and ecosystem sustainability. Ocean climate change (‘CC’) modelling may become a key decision‐support tool for MSP, but traditional modelling analysis and communication challenges prevent their broad uptake. We employed MSP‐specific ocean climate modelling analyses to inform a real‐life MSP process; addressing how nature conservation and fisheries could be adapted to CC. We found that the currently planned distribution of these activities may become unsustainable during the policy's implementation due to CC, leading to a shortfall in its sustainability and blue growth targets. Significant, climate‐driven ecosystem‐level shifts in ocean components underpinning designated sites and fishing activity were estimated, reflecting different magnitudes of shifts in benthic versus pelagic, and inshore versus offshore habitats. Supporting adaptation, we then identified: CC refugia (areas where the ecosystem remains within the boundaries of its present state); CC hotspots (where climate drives the ecosystem towards a new state, inconsistent with each sectors’ present use distribution); and for the first time, identified bright spots (areas where oceanographic processes drive range expansion opportunities that may support sustainable growth in the medium term). We thus create the means to: identify where sector‐relevant ecosystem change is attributable to CC; incorporate resilient delivery of conservation and sustainable ecosystem management aims into MSP; and to harness opportunities for blue growth where they exist. Capturing CC bright spots alongside refugia within protected areas may present important opportunities to meet sustainability targets while helping support the fishing sector in a changing climate. By capitalizing on the natural distribution of climate resilience within ocean ecosystems, such climate‐adaptive spatial management strategies could be seen as nature‐based solutions to limit the impact of CC on ocean ecosystems and dependent blue economy sectors, paving the way for climate‐smart MSP.

Field testing cellulose-water oxygen isotope relations in periphyton for paleohydrological reconstructions - Cory A. M. Savage; Casey R. Remmer; James V. Telford; Mitchell L. Kay; Eva Mehler; Brent B. Wolfe; Roland I. Hall (Journal of Paleolimnology, 2021)

Plastic Pollution and Small Juvenile Marine Turtles: A Potential Evolutionary Trap - Emily M. Duncan; Annette C. Broderick; Kay Critchell; Tamara S. Galloway; Mark Hamann; Colin J. Limpus; Penelope K. Lindeque; David Santillo; Anton D. Tucker; Scott Whiting; Erina J. Young; Brendan J. Godley (Frontiers in Marine Science, 2021)
The ingestion of plastic by marine turtles is now reported for all species. Small juvenile turtles (including post-hatchling and oceanic juveniles) are thought to be most at risk, due to feeding preferences and overlap with areas of high plastic abundance. Their remote and dispersed life stage, however, results in limited access and assessments. Here, stranded and bycaught specimens from Queensland Australia, Pacific Ocean (PO; n = 65; 1993–2019) and Western Australia, Indian Ocean (IO; n = 56; 2015–2019) provide a unique opportunity to assess the extent of plastic (> 1mm) ingestion in five species [green ( Chelonia mydas ), loggerhead ( Caretta caretta ), hawksbill ( Eretmochelys imbricata ), olive ridley ( Lepidochelys olivacea ), and flatback turtles ( Natator depressus )]. In the Pacific Ocean, high incidence of ingestion occurred in green (83%; n = 36), loggerhead (86%; n = 7), flatback (80%; n = 10) and olive ridley turtles (29%; n = 7). There was an overall lower incidence in IO; highest being in the flatback (28%; n = 18), the loggerhead (21%; n = 14) and green (9%; n = 22). No macroplastic debris ingestion was documented for hawksbill turtles in either site although sample sizes were smaller for this species (PO n = 5; IO n = 2). In the Pacific Ocean, the majority of ingested debris was made up of hard fragments (mean of all species 52%; species averages 46–97%), whereas for the Indian Ocean these were filamentous plastics (52%; 43–77%). The most abundant colour for both sites across all species was clear (PO: 36%; IO: 39%), followed by white for PO (36%) then green and blue for IO (16%; 16%). The polymers most commonly ingested by turtles in both oceans were polyethylene (PE; PO-58%; IO-39%) and polypropylene (PP; PO-20.2%; IO-23.5%). We frame the high occurrence of ingested plastic present in this marine turtle life stage as a potential evolutionary trap as they undertake their development in what are now some of the most polluted areas of the global oceans.

Inflammation biomarkers associated with arsenic exposure by drinking water and respiratory outcomes in indigenous children from three Yaqui villages in southern Sonora, México - Christian B. Vega-Millán; Ana G. Dévora-Figueroa; Jefferey L. Burgess; Paloma I. Beamer; Melissa Furlong; R. Clark Lantz; Diana Meza-Figueroa; Mary Kay O´Rourke; Leticia García-Rico; Edna R. Meza-Escalante; José J. Balderas-Cortés; Maria M. Meza-Montenegro (Environmental Science and Pollution Research, 2021)

The Possession of Coccoliths Fails to Deter Microzooplankton Grazers - Kyle M. J. Mayers; Alex J. Poulton; Kay Bidle; Kimberlee Thamatrakoln; Brittany Schieler; Sarah L. C. Giering; Seona R. Wells; Glen A. Tarran; Dan Mayor; Matthew Johnson; Ulf Riebesell; Aud Larsen; et al. (Frontiers in Marine Science, 2020)
Phytoplankton play a central role in the regulation of global carbon and nutrient cycles, forming the basis of the marine food webs. A group of biogeochemically important phytoplankton, the coccolithophores, produce calcium carbonate scales that have been hypothesized to deter or reduce grazing by microzooplankton. Here, a meta-analysis of mesocosm-based experiments demonstrates that calcification of the cosmopolitan coccolithophore, Emiliania huxleyi , fails to deter microzooplankton grazing. The median grazing to growth ratio for E. huxleyi (0.56 ± 0.40) was not significantly different among non-calcified nano- or picoeukaryotes (0.71 ± 0.31 and 0.55 ± 0.34, respectively). Additionally, the environmental concentration of E. huxleyi did not drive preferential grazing of non-calcified groups. These results strongly suggest that the possession of coccoliths does not provide E. huxleyi effective protection from microzooplankton grazing. Such indiscriminate consumption has implications for the dissolution and fate of CaCO 3 in the ocean, and the evolution of coccoliths.

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: Myanmar amber - Joachim T. Haug; Dany Azar; Andrew Ross; Jacek Szwedo; Bo Wang; Antonio Arillo; Viktor Baranov; Julia Bechteler; Rolf Beutel; Vladimir Blagoderov; Xavier Delclòs; Jason Dunlop; et al. (PalZ, 2020)

The interaction of physical and biological factors drives phytoplankton spatial distribution in the northern California Current - Jeffrey W. Krause; Mark A. Brzezinski; John L. Largier; Heather M. McNair; Michael Maniscalco; Kay D. Bidle; Andrew E. Allen; Kimberlee Thamatrakoln (Limnology and Oceanography, 2020)
Transitions in phytoplankton community composition are typically attributed to ecological succession even in physically dynamic upwelling systems like the California Current Ecosystem (CCE). An expected succession from a high‐chlorophyll (~ 10 μ g L −1 ) diatom‐dominated assemblage to a low‐chlorophyll ( μ g L −1 ) non‐diatom dominated assemblage was observed during a 2013 summer upwelling event in the CCE. Using an interdisciplinary field‐based space‐for‐time approach leveraging both biogeochemical rate measurements and metatranscriptomics, we suggest that this successional pattern was driven primarily by physical processes. An annually recurring mesoscale eddy‐like feature transported significant quantities of high‐phytoplankton‐biomass coastal water offshore. Chlorophyll was diluted during transport, but diatom contributions to phytoplankton biomass and activity (49–62% observed) did not decline to the extent predicted by dilution (18–24% predicted). Under the space‐for‐time assumption, these trends infer diatom biomass and activity and were stimulated during transport. This is hypothesized to result from decreased contact rates with mortality agents (e.g., viruses) and release from nutrient limitation (confirmed by rate data nearshore), as predicted by the Disturbance‐Recovery hypothesis of phytoplankton bloom formation. Thus, the end point taxonomic composition and activity of the phytoplankton assemblage being transported by the eddy‐like feature were driven by physical processes (mixing) affecting physiological (release from nutrient limitation, increased growth) and ecological (reduced mortality) factors that favored the persistence of the nearshore diatoms during transit. The observed connection between high‐diatom‐biomass coastal waters and non‐diatom‐dominated offshore waters supports the proposed mechanisms for this recurring eddy‐like feature moving seed populations of coastal phytoplankton offshore and thereby sustaining their activity.

A genome-wide association study implicates the BMP7 locus as a risk factor for nonsyndromic metopic craniosynostosis - Cristina M. Justice; Araceli Cuellar; Krithi Bala; Jeremy A. Sabourin; Michael L. Cunningham; Karen Crawford; Julie M. Phipps; Yan Zhou; Deirdre Cilliers; Jo C. Byren; David Johnson; Steven A. Wall; et al. (Human Genetics, 2020)

Assessment of the Skill of Coupled Physical–Biogeochemical Models in the NW Mediterranean - Eduardo Ramirez-Romero; Gabriel Jordà; Angel Amores; Susan Kay; Mariona Segura-Noguera; Diego M. Macias; Francesc Maynou; Ana Sabatés; Ignacio A. Catalán (Frontiers in Marine Science, 2020)

Patient attitudes towards brain donation across both neurodegenerative and non-neurodegenerative neurological disorders - Reudi J. W. Chan; Sherilyn Seah; Joel Y. J. Foo; Alisa C. W. Yong; Nicole S. Y. Chia; Sherwin J. U. Agustin; Shermyn X. M. Neo; Kay-Yaw Tay; Wing-Lok Au; Louis C. S. Tan; Adeline S. L. Ng (Cell and Tissue Banking, 2020)

Method development for rapid quantification of Rn-222 in surface water and groundwater - Charles J. B. Gowing; James M. Dinsley; Elizabeth L. Gallannaugh; Pauline L. Smedley; Andrew L. Marriott; Michael J. Bowes; Kay A. Green; Michael J. Watts (Environmental Geochemistry and Health, 2020)

Global fern and lycophyte richness explained: How regional and local factors shape plot richness - Anna Weigand; Stefan Abrahamczyk; Isabelle Aubin; Claudia Bita‐Nicolae; Helge Bruelheide; Cesar I. Carvajal‐Hernández; Daniele Cicuzza; Lucas Erickson Nascimento da Costa; János Csiky; Jürgen Dengler; André Luís de Gasper; Greg R. Guerin; et al. (Journal of Biogeography, 2020)
Aim To disentangle the influence of environmental factors at different spatial grains (regional and local) on fern and lycophyte species richness and to ask how regional and plot‐level richness are related to each other. Location Global. Taxon Ferns and lycophytes. Methods We explored fern and lycophyte species richness at two spatial grains, regional (hexagonal grid cells of 7,666 km 2 ) and plot level (300–500 m 2 ), in relation to environmental data at regional and local grains (the 7,666 km 2 hexagonal grid cells and 4 km 2 square grid cells, respectively). For the regional grain, we obtained species richness data for 1,243 spatial units and used them together with climatic and topographical predictors to model global fern richness. For the plot‐level grain, we collated a global dataset of nearly 83,000 vegetation plots with a surface area in the range 300–500 m 2 in which all fern and lycophyte species had been counted. We used structural equation modelling to identify which regional and local factors have the biggest effect on plot‐level fern and lycophyte species richness worldwide. We investigate how plot‐level richness is related to modelled regional richness at the plot's location. Results Plot‐level fern and lycophyte species richness were best explained by models allowing a link between regional environment and plot‐level richness. A link between regional richness and plot‐level richness was essential, as models without it were rejected, while models without the regional environment‐plot‐level richness link were still valid but had a worse goodness‐of‐fit value. Plot‐level richness showed a hump‐shaped relationship with regional richness. Main conclusions Regional environment and regional fern and lycophyte species richness each are important determinants of plot‐level richness, and the inclusion of one does not substitute the inclusion of the other. Plot‐level richness increases with regional richness until a saturation point is reached, after which plot‐level richness decreases despite increasing regional richness, possibly reflecting species interactions.

Artificial intelligence supported patient self-care in chronic heart failure: a paradigm shift from reactive to predictive, preventive and personalised care - Matthew Barrett; Josiane Boyne; Julia Brandts; Hans-Peter Brunner-La Rocca; Lieven De Maesschalck; Kurt De Wit; Lana Dixon; Casper Eurlings; Donna Fitzsimons; Olga Golubnitschaja; Arjan Hageman; Frank Heemskerk; et al. (EPMA Journal, 2019)
Heart failure (HF) is one of the most complex chronic disorders with high prevalence, mainly due to the ageing population and better treatment of underlying diseases. Prevalence will continue to rise and is estimated to reach 3% of the population in Western countries by 2025. It is the most important cause of hospitalisation in subjects aged 65 years or more, resulting in high costs and major social impact. The current “one-size-fits-all” approach in the treatment of HF does not result in best outcome for all patients. These facts are an imminent threat to good quality management of patients with HF. An unorthodox approach from a new vision on care is required. We propose a novel predictive, preventive and personalised medicine approach where patients are truly leading their management, supported by an easily accessible online application that takes advantage of artificial intelligence. This strategy paper describes the needs in HF care, the needed paradigm shift and the elements that are required to achieve this shift. Through the inspiring collaboration of clinical and high-tech partners from North-West Europe combining state of the art HF care, artificial intelligence, serious gaming and patient coaching, a virtual doctor is being created. The results are expected to advance and personalise self-care, where standard care tasks are performed by the patients themselves, in principle without involvement of healthcare professionals, the latter being able to focus on complex conditions. This new vision on care will significantly reduce costs per patient while improving outcomes to enable long-term sustainability of top-level HF care.

Attitudes of Asian Parkinson patients towards brain donation - Shazma Khan; Joel Y. J. Foo; Nicole S. Y. Chia; Sherwin J. U. Agustin; Shermyn X. M. Neo; Kay-Yaw Tay; Wing-Lok Au; Adeline S. L. Ng; Louis C. S. Tan (Cell and Tissue Banking, 2019)

Early life social and ecological determinants of global DNA methylation in wild spotted hyenas - Zachary M. Laubach; Christopher D. Faulk; Dana C. Dolinoy; Luke Montrose; Tamara R. Jones; Donna Ray; Malit O. Pioon; Kay E. Holekamp (Molecular Ecology, 2019)
Environmental factors early in life can have lasting influence on the development and phenotypes of animals, but the underlying molecular modifications remain poorly understood. We examined cross‐sectional associations among early life socioecological factors and global DNA methylation in 293 wild spotted hyenas ( Crocuta crocuta ) in the Masai Mara National Reserve, Kenya, grouped according to three age classes (cub, subadult and adult). Explanatory variables of interest included annual maternal rank based on outcomes of dyadic agonistic interactions, litter size, wild ungulate prey density and anthropogenic disturbance in the year each hyena was born based on counts of illegal livestock in the Reserve. The dependent variable of interest was global DNA methylation, assessed via the LUminometric Methylation Assay, which provides a percentage methylation value calculated at CCGG sites across the genome. Among cubs, we observed approximately 2.75% higher CCGG methylation in offspring born to high‐ than low‐ranking mothers. Among cubs and subadults, higher anthropogenic disturbance corresponded with greater %CCGG methylation. In both cubs and adults, we found an inverse association between prey density measured before a hyena was 3 months old and %CCGG methylation. Our results suggest that maternal rank, anthropogenic disturbance and prey availability early in life are associated with later life global DNA methylation. Future studies are required to understand the extent to which these DNA methylation patterns relate to adult phenotypes and fitness outcomes.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Volatiles of pathogenic and non-pathogenic soil-borne fungi affect plant development and resistance to insects - Kay Moisan; Viviane Cordovez; Els M. van de Zande; Jos M. Raaijmakers; Marcel Dicke; Dani Lucas-Barbosa (Oecologia, 2019)

Chalcophile element fertility and the formation of porphyry Cu ± Au deposits - Jung-Woo Park; Ian H. Campbell; Sanjeewa P. K. Malaviarachchi; Helen Cocker; Hongda Hao; Suzanne M. Kay (Mineralium Deposita, 2019)

Biochemical diversity of glycosphingolipid biosynthesis as a driver of Coccolithovirus competitive ecology - Jozef I. Nissimov; David Talmy; Liti Haramaty; Helen F. Fredricks; Ehud Zelzion; Ben Knowles; A. Murat Eren; Rebecca Vandzura; Christien P. Laber; Brittany M. Schieler; Christopher T. Johns; Kuldeep D. More; et al. (Environmental Microbiology, 2019)
Summary Coccolithoviruses (EhVs) are large, double‐stranded DNA‐containing viruses that infect the single‐celled, marine coccolithophore Emiliania huxleyi . Given the cosmopolitan nature and global importance of E. huxleyi as a bloom‐forming, calcifying, photoautotroph, E. huxleyi –EhV interactions play a key role in oceanic carbon biogeochemistry. Virally‐encoded glycosphingolipids (vGSLs) are virulence factors that are produced by the activity of virus‐encoded serine palmitoyltransferase (SPT). Here, we characterize the dynamics, diversity and catalytic production of vGSLs in an array of EhV strains in relation to their SPT sequence composition and explore the hypothesis that they are a determinant of infectivity and host demise. vGSL production and diversity was positively correlated with increased virulence, virus replication rate and lytic infection dynamics in laboratory experiments, but they do not explain the success of less‐virulent EhVs in natural EhV communities. The majority of EhV‐derived SPT amplicon sequences associated with infected cells in the North Atlantic derived from slower infecting, less virulent EhVs. Our lab‐, field‐ and mathematical model‐based data and simulations support ecological scenarios whereby slow‐infecting, less‐virulent EhVs successfully compete in North Atlantic populations of E. huxleyi , through either the preferential removal of fast‐infecting, virulent EhVs during active infection or by having access to a broader host range.

From Observation to Information and Users: The Copernicus Marine Service Perspective - Pierre Yves Le Traon; Antonio Reppucci; Enrique Alvarez Fanjul; Lotfi Aouf; Arno Behrens; Maria Belmonte; Abderrahim Bentamy; Laurent Bertino; Vittorio Ernesto Brando; Matilde Brandt Kreiner; Mounir Benkiran; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

Building actor-centric transformative capacity through city-university partnerships - Lauren Withycombe Keeler; Fletcher Beaudoin; Arnim Wiek; Beatrice John; Amy M. Lerner; Richard Beecroft; Kaidi Tamm; Andreas Seebacher; Daniel J. Lang; Braden Kay; Nigel Forrest (Ambio, 2019)

Partial congruence in habitat patterns for taxonomic and functional diversity of fish assemblages in seagrass ecosystems - Melisa C. Wong; Lauren M. Kay (Marine Biology, 2019)

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Overexpressed in colorectal carcinoma gene (OCC-1) upregulation and APPL2 gene downregulation in breast cancer specimens - Abolfazl Ghalaei; Maryam Kay; Shiva Zarrinfam; Parisa Hoseinpour; Mehrdad Behmanesh; Bahram M. Soltani (Molecular Biology Reports, 2018)

Population genetics of the endangered Maugean skate (Zearaja maugeana) in Macquarie Harbour, Tasmania - Kay Weltz; Jeremy M. Lyle; Jayson M. Semmens; Jennifer R. Ovenden (Conservation Genetics, 2018)

Functional analysis of Salmonella Typhi adaptation to survival in water - Robert A. Kingsley; Gemma Langridge; Sarah E. Smith; Carine Makendi; Maria Fookes; Tom M. Wileman; Moataz Abd El Ghany; A. Keith Turner; Zoe A. Dyson; Sushmita Sridhar; Derek Pickard; Sally Kay; et al. (Environmental Microbiology, 2018)
Summary Contaminated water is a major risk factor associated with the transmission of Salmonella enterica serovar Typhi ( S. Typhi), the aetiological agent of human typhoid. However, little is known about how this pathogen adapts to living in the aqueous environment. We used transcriptome analysis (RNA‐seq) and transposon mutagenesis (TraDIS) to characterize these adaptive changes and identify multiple genes that contribute to survival. Over half of the genes in the S. Typhi genome altered expression level within the first 24 h following transfer from broth culture to water, although relatively few did so in the first 30 min. Genes linked to central metabolism, stress associated with arrested proton motive force and respiratory chain factors changed expression levels. Additionally, motility and chemotaxis genes increased expression, consistent with a scavenging lifestyle. The viaB‐associated gene tviC encoding a glcNAc epimerase that is required for Vi polysaccharide biosynthesis was, along with several other genes, shown to contribute to survival in water. Thus, we define regulatory adaptation operating in S. Typhi that facilitates survival in water.

Identification of a novel intergenic miRNA located between the human DDC and COBL genes with a potential function in cell cycle arrest - Mohamad Hussein Hoballa; Bahram M. Soltani; Seyed Javad Mowla; Mojgan Sheikhpour; Maryam Kay (Molecular and Cellular Biochemistry, 2018)

Differential cellular responses by oncogenic levels of c-Myc expression in long-term confluent retinal pigment epithelial cells - Yiping Wang; Xiangdong Cheng; Muhammad Kaleem Samma; Sam K. P. Kung; Clement M. Lee; Sung Kay Chiu (Molecular and Cellular Biochemistry, 2018)

Sympatric serpentine endemic Monardella (Lamiaceae) species maintain habitat differences despite hybridization - Kathleen M. Kay; Suzie Woolhouse; Brett A. Smith; Nathaniel S. Pope; Nishanta Rajakaruna (Molecular Ecology, 2018)
Ecological differentiation and genetic isolation are thought to be critical in facilitating coexistence between related species, but the relative importance of these phenomena and the interactions between them are not well understood. Here, we examine divergence in abiotic habitat affinity and the extent of hybridization and introgression between two rare species of Monardella (Lamiaceae) that are both restricted to the same serpentine soil exposure in California. Although broadly sympatric, they are found in microhabitats that differ consistently in soil chemistry, slope, rockiness and vegetation. We identify one active hybrid zone at a site with intermediate soil and above‐ground characteristics, and we document admixture patterns indicative of extensive and asymmetric introgression from one species into the other. We find that genetic distance among heterospecific populations is related to geographic distance, such that the extent of apparent introgression is partly explained by the spatial proximity to the hybrid zone. Our work shows that plant species can maintain morphological and ecological integrity in the face of weak genetic isolation, intermediate habitats can facilitate the establishment of hybrids, and that the degree of apparent introgression a population experiences is related to its geographic location rather than its local habitat characteristics.

Increased grassland arthropod production with mammalian herbivory and eutrophication: a test of mediation pathways - Eric M. Lind; Kimberly J. La Pierre; Eric W. Seabloom; Juan Alberti; Oscar Iribarne; Jennifer Firn; Daniel S. Gruner; Adam D. Kay; Jesus Pascal; Justin P. Wright; Louie Yang; Elizabeth T. Borer (Ecology, 2017)
Increases in nutrient availability and alterations to mammalian herbivore communities are a hallmark of the Anthropocene, with consequences for the primary producer communities in many ecosystems. While progress has advanced understanding of plant community responses to these perturbations, the consequences for energy flow to higher trophic levels in the form of secondary production are less well understood. We quantified arthropod biomass after manipulating soil nutrient availability and wild mammalian herbivory, using identical methods across 13 temperate grasslands. Of experimental increases in nitrogen, phosphorus, and potassium, only treatments including nitrogen resulted in significantly increased arthropod biomass. Wild mammalian herbivore removal had a marginal, negative effect on arthropod biomass, with no interaction with nutrient availability. Path analysis including all sites implicated nutrient content of the primary producers as a driver of increased arthropod mean size, which we confirmed using 10 sites for which we had foliar nutrient data. Plant biomass and physical structure mediated the increase in arthropod abundance, while the nitrogen treatments accounted for additional variation not explained by our measured plant variables. The mean size of arthropod individuals was 2.5 times more influential on the plot‐level total arthropod biomass than was the number of individuals. The eutrophication of grasslands through human activity, especially nitrogen deposition, thus may contribute to higher production of arthropod consumers through increases in nutrient availability across trophic levels.

Satellite Observations of Phytoplankton Functional Type Spatial Distributions, Phenology, Diversity, and Ecotones - Tiffany A. Moisan; Kay M. Rufty; John R. Moisan; Matthew A. Linkswiler (Frontiers in Marine Science, 2017)

Effects of interspecific gene flow on the phenotypic variance–covariance matrix in Lake Victoria Cichlids - Kay Lucek; Lucie Greuter; Oliver M. Selz; Ole Seehausen (Hydrobiologia, 2017)

Direct measurements of the light dependence of gross photosynthesis and oxygen consumption in the ocean - Benjamin Bailleul; Jisoo Park; Christopher M. Brown; Kay D. Bidle; Sang Hoon Lee; Paul G. Falkowski (Limnology and Oceanography, 2017)
We measured the light dependence of gross photosynthesis and oxygen uptake rates by membrane inlet mass spectrometry in two open ocean regions: the Amundsen Sea (Antarctica), dominated by Phaeocystis antarctica , and the North Atlantic, dominated by Emiliania huxleyi . In the North Atlantic, respiration was independent of irradiance and was higher than the gross photosynthetic rate at all irradiances. In contrast, in the Amundsen Sea, oxygen uptake processes were light dependent; dark respiration was one order of magnitude lower than the maximal gross photosynthetic rate, but the oxygen uptake rate increased by 10 fold at surface irradiances. Our results suggest the light dependence of oxygen uptake in Amundsen Sea has two sources: one is independent of photosynthesis, and is possibly associated with the photo‐reduction of O 2 mediated by dissolved organic matter; the second reflects the activity of an oxidase fueled in the light with photosynthetic electron flow. Our results highlight the importance of improving our understanding of oxygen consuming reactions in the euphotic zone.

Warm discharges in cold fresh water: 2. Numerical simulation of laminar line plumes - Alabodite M. George; Anthony Kay (Environmental Fluid Mechanics, 2017)

How economics can further the success of ecological restoration - Md Sayed Iftekhar; Maksym Polyakov; Dean Ansell; Fiona Gibson; Geoffrey M. Kay (Conservation Biology, 2017)
Restoration scientists and practitioners have recently begun to include economic and social aspects in the design and investment decisions for restoration projects. With few exceptions, ecological restoration studies that include economics focus solely on evaluating costs of restoration projects. However, economic principles, tools, and instruments can be applied to a range of other factors that affect project success. We considered the relevance of applying economics to address 4 key challenges of ecological restoration: assessing social and economic benefits, estimating overall costs, project prioritization and selection, and long‐term financing of restoration programs. We found it is uncommon to consider all types of benefits (such as nonmarket values) and costs (such as transaction costs) in restoration programs. Total benefit of a restoration project can be estimated using market prices and various nonmarket valuation techniques. Total cost of a project can be estimated using methods based on property or land‐sale prices, such as hedonic pricing method and organizational surveys. Securing continuous (or long‐term) funding is also vital to accomplishing restoration goals and can be achieved by establishing synergy with existing programs, public–private partnerships, and financing through taxation.

Effects of past and present livestock grazing on herpetofauna in a landscape‐scale experiment - Geoffrey M. Kay; Alessio Mortelliti; Ayesha Tulloch; Philip Barton; Daniel Florance; Saul A. Cunningham; David B. Lindenmayer (Conservation Biology, 2017)
Livestock grazing is the most widespread land use on Earth and can have negative effects on biodiversity. Yet, many of the mechanisms by which grazing leads to changes in biodiversity remain unresolved. One reason is that conventional grazing studies often target broad treatments rather than specific parameters of grazing (e.g., intensity, duration, and frequency) or fail to account for historical grazing effects. We conducted a landscape‐scale replicated grazing experiment (15,000 km 2 , 97 sites) to examine the impact of past grazing management and current grazing regimes (intensity, duration, and frequency) on a community of ground‐dwelling herpetofauna (39 species). We analyzed community variables (species richness and composition) for all species and built multiseason patch‐occupancy models to predict local colonization and extinction for the 7 most abundant species. Past grazing practices did not influence community richness but did affect community composition and patch colonization and extinction for 4 of 7 species. Present grazing parameters did not influence community richness or composition, but 6 of the 7 target species were affected by at least one grazing parameter. Grazing frequency had the most consistent influence, positively affecting 3 of 7 species (increased colonization or decreased extinction). Past grazing practice affected community composition and population dynamics in some species in different ways, which suggests that conservation planners should examine the different grazing histories of an area. Species responded differently to specific current grazing practices; thus, incentive programs that apply a diversity of approaches rather than focusing on a change such as reduced grazing intensity should be considered. Based on our findings, we suggest that determining fine‐scale grazing attributes is essential for advancing grazing as a conservation strategy.

Inferring infection hazard in wildlife populations by linking data across individual and population scales - Kim M. Pepin; Shannon L. Kay; Ben D. Golas; Susan S. Shriner; Amy T. Gilbert; Ryan S. Miller; Andrea L. Graham; Steven Riley; Paul C. Cross; Michael D. Samuel; Mevin B. Hooten; Jennifer A. Hoeting; et al. (Ecology Letters, 2017)
Our ability to infer unobservable disease‐dynamic processes such as force of infection (infection hazard for susceptible hosts) has transformed our understanding of disease transmission mechanisms and capacity to predict disease dynamics. Conventional methods for inferring FOI estimate a time‐averaged value and are based on population‐level processes. Because many pathogens exhibit epidemic cycling and FOI is the result of processes acting across the scales of individuals and populations, a flexible framework that extends to epidemic dynamics and links within‐host processes to FOI is needed. Specifically, within‐host antibody kinetics in wildlife hosts can be short‐lived and produce patterns that are repeatable across individuals, suggesting individual‐level antibody concentrations could be used to infer time since infection and hence FOI . Using simulations and case studies (influenza A in lesser snow geese and Yersinia pestis in coyotes), we argue that with careful experimental and surveillance design, the population‐level FOI signal can be recovered from individual‐level antibody kinetics, despite substantial individual‐level variation. In addition to improving inference, the cross‐scale quantitative antibody approach we describe can reveal insights into drivers of individual‐based variation in disease response, and the role of poorly understood processes such as secondary infections, in population‐level dynamics of disease.

The basis function approach for modeling autocorrelation in ecological data - Trevor J. Hefley; Kristin M. Broms; Brian M. Brost; Frances E. Buderman; Shannon L. Kay; Henry R. Scharf; John R. Tipton; Perry J. Williams; Mevin B. Hooten (Ecology, 2017)
Analyzing ecological data often requires modeling the autocorrelation created by spatial and temporal processes. Many seemingly disparate statistical methods used to account for autocorrelation can be expressed as regression models that include basis functions. Basis functions also enable ecologists to modify a wide range of existing ecological models in order to account for autocorrelation, which can improve inference and predictive accuracy. Furthermore, understanding the properties of basis functions is essential for evaluating the fit of spatial or time‐series models, detecting a hidden form of collinearity, and analyzing large data sets. We present important concepts and properties related to basis functions and illustrate several tools and techniques ecologists can use when modeling autocorrelation in ecological data.

Regional differences and linkage between canopy structure and community composition of rockweed habitats in Atlantic Canada - Lauren M. Kay; Tyler D. Eddy; Allison L. Schmidt; Heike K. Lotze (Marine Biology, 2016)

Introducing molaR: a New R Package for Quantitative Topographic Analysis of Teeth (and Other Topographic Surfaces) - James D. Pampush; Julia M. Winchester; Paul E. Morse; Alexander Q. Vining; Doug M. Boyer; Richard F. Kay (Journal of Mammalian Evolution, 2016)

Copy-number variant analysis of classic heterotaxy highlights the importance of body patterning pathways - Erin M. Hagen; Robert J. Sicko; Denise M. Kay; Shannon L. Rigler; Aggeliki Dimopoulos; Shabbir Ahmad; Margaret H. Doleman; Ruzong Fan; Paul A. Romitti; Marilyn L. Browne; Michele Caggana; Lawrence C. Brody; et al. (Human Genetics, 2016)

The Curious Nature of the Hemispheric Symmetry of the Earth’s Water and Energy Balances - Graeme L. Stephens; Maria Z. Hakuba; Matt Hawcroft; Jim M. Haywood; Ali Behrangi; Jennifer E. Kay; Peter J Webster (Current Climate Change Reports, 2016)

Solutions for ecosystem‐level protection of ocean systems under climate change - Ana M. Queirós; Klaus B. Huebert; Friedemann Keyl; Jose A. Fernandes; Willem Stolte; Marie Maar; Susan Kay; Miranda C. Jones; Katell G. Hamon; Gerrit Hendriksen; Youen Vermard; Paul Marchal; et al. (Global Change Biology, 2016)
The Paris Conference of Parties ( COP 21) agreement renewed momentum for action against climate change, creating the space for solutions for conservation of the ocean addressing two of its largest threats: climate change and ocean acidification ( CCOA ). Recent arguments that ocean policies disregard a mature conservation research field and that protected areas cannot address climate change may be oversimplistic at this time when dynamic solutions for the management of changing oceans are needed. We propose a novel approach, based on spatial meta‐analysis of climate impact models, to improve the positioning of marine protected areas to limit CCOA impacts. We do this by estimating the vulnerability of ocean ecosystems to CCOA in a spatially explicit manner and then co‐mapping human activities such as the placement of renewable energy developments and the distribution of marine protected areas. We test this approach in the NE Atlantic considering also how CCOA impacts the base of the food web which supports protected species, an aspect often neglected in conservation studies. We found that, in this case, current regional conservation plans protect areas with low ecosystem‐level vulnerability to CCOA , but disregard how species may redistribute to new, suitable and productive habitats. Under current plans, these areas remain open to commercial extraction and other uses. Here, and worldwide, ocean conservation strategies under CCOA must recognize the long‐term importance of these habitat refuges, and studies such as this one are needed to identify them. Protecting these areas creates adaptive, climate‐ready and ecosystem‐level policy options for conservation, suitable for changing oceans.

A non-canonical role for desmoglein-2 in endothelial cells: implications for neoangiogenesis - Lisa M. Ebert; Lih Y. Tan; M. Zahied Johan; Kay Khine Myo Min; Michaelia P. Cockshell; Kate A. Parham; Kelly L. Betterman; Paceman Szeto; Samantha Boyle; Lokugan Silva; Angela Peng; YouFang Zhang; et al. (Angiogenesis, 2016)

Using empirical models of species colonization under multiple threatening processes to identify complementary threat‐mitigation strategies - Ayesha I.T. Tulloch; Alessio Mortelliti; Geoffrey M. Kay; Daniel Florance; David Lindenmayer (Conservation Biology, 2016)
Approaches to prioritize conservation actions are gaining popularity. However, limited empirical evidence exists on which species might benefit most from threat mitigation and on what combination of threats, if mitigated simultaneously, would result in the best outcomes for biodiversity. We devised a way to prioritize threat mitigation at a regional scale with empirical evidence based on predicted changes to population dynamics—information that is lacking in most threat‐management prioritization frameworks that rely on expert elicitation. We used dynamic occupancy models to investigate the effects of multiple threats (tree cover, grazing, and presence of an hyperaggressive competitor, the Noisy Miner (Manorina melanocephala) on bird‐population dynamics in an endangered woodland community in southeastern Australia. The 3 threatening processes had different effects on different species. We used predicted patch‐colonization probabilities to estimate the benefit to each species of removing one or more threats. We then determined the complementary set of threat‐mitigation strategies that maximized colonization of all species while ensuring that redundant actions with little benefit were avoided. The single action that resulted in the highest colonization was increasing tree cover, which increased patch colonization by 5% and 11% on average across all species and for declining species, respectively. Combining Noisy Miner control with increasing tree cover increased species colonization by 10% and 19% on average for all species and for declining species respectively, and was a higher priority than changing grazing regimes. Guidance for prioritizing threat mitigation is critical in the face of cumulative threatening processes. By incorporating population dynamics in prioritization of threat management, our approach helps ensure funding is not wasted on ineffective management programs that target the wrong threats or species.

Human islet cells are killed by BID-independent mechanisms in response to FAS ligand - Mugdha V. Joglekar; Prerak M. Trivedi; Thomas W. Kay; Wayne J. Hawthorne; Philip J. O’Connell; Alicia J. Jenkins; Anandwardhan A. Hardikar; Helen E. Thomas (Apoptosis, 2016)

Molecular tools for bathing water assessment in Europe: Balancing social science research with a rapidly developing environmental science evidence-base - David M. Oliver; Nick D. Hanley; Melanie van Niekerk; David Kay; A. Louise Heathwaite; Sharyl J. M. Rabinovici; Julie L. Kinzelman; Lora E. Fleming; Jonathan Porter; Sabina Shaikh; Rob Fish; Sue Chilton; et al. (Ambio, 2016)

Functional response of the isolated, perfused normoxic heart to pyruvate dehydrogenase activation by dichloroacetate and pyruvate - Rafael Jaimes; Sarah Kuzmiak-Glancy; Daina M. Brooks; Luther M. Swift; Nikki G. Posnack; Matthew W. Kay (Pflügers Archiv - European Journal of Physiology, 2016)

Effects of increasing water temperatures on survival and growth of ecologically and economically important seaweeds in Atlantic Canada: implications for climate change - Kristen L. Wilson; Lauren M. Kay; Allison L. Schmidt; Heike K. Lotze (Marine Biology, 2015)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

BCL2 protein signalling determines acute responses to neoadjuvant chemoradiotherapy in rectal cancer - L. Flanagan; A. U. Lindner; C. de Chaumont; J. Kehoe; J. Fay; O. Bacon; S. Toomey; H. J. Huber; B. T. Hennessy; E. W. Kay; D. A. McNamara; J. H. M. Prehn (Journal of Molecular Medicine, 2015)

An investigation of the effect of transient climate change on snowmelt, flood frequency and timing in northern Britain - A. L. Kay; S. M. Crooks (International Journal of Climatology, 2014)
Climate change is almost certain to affect snow and ice processes. Even at lower latitudes, changes in snow cover at high altitudes can significantly affect catchment hydrology. This article uses data from a transient Regional Climate Model projection ( HadRM3Q0 ) for 1950–2099 ( A1B emissions) to drive hydrological models for three nested catchments on the river Dee in north‐east Scotland, to assess potential changes in flood frequency and timing using annual maxima and moving‐window analyses. Some results are also shown for an upland catchment in northern England. Modelling is performed both with and without a snow module, to demonstrate the effects of snowfall/melt and how these change through time and vary between catchments. Modelled changes in flood magnitude and timing are nonlinear, with most changes for daily mean flows not significant. For longer duration (30‐day) flows with snow there are significant decreases in peak magnitude, particularly for the smaller higher altitude Dee catchments, with peaks occurring months earlier in future (changes without snow are generally not significant). There is a general convergence in results with and without snow later in the period, as snow processes become less important, but convergence occurs at different times for different catchments and occurs differently for daily and 30‐day peak flows due to the differential effects of snow at different durations. This not only highlights the importance of including snow processes for such catchments, particularly for longer duration flows, but also highlights the complexity of interactions: Physical catchment properties, the balance between precipitation occurrence and temperature, and how this balance alters as the climate changes will each be critical in determining the impact on the magnitude and timing of peak flows, making it hard to generalize results.

Porcine reproductive and respiratory syndrome (PRRS): an immune dysregulatory pandemic - J. E. Butler; K. M. Lager; William Golde; Kay S. Faaberg; Marek Sinkora; Crystal Loving; Y. I. Zhang (Immunologic Research, 2014)

Probabilistic impacts of climate change on flood frequency using response surfaces I: England and Wales - A. L. Kay; S. M. Crooks; H. N. Davies; C. Prudhomme; N. S. Reynard (Regional Environmental Change, 2014)

Probabilistic impacts of climate change on flood frequency using response surfaces II: Scotland - A. L. Kay; S. M. Crooks; H. N. Davies; N. S. Reynard (Regional Environmental Change, 2014)

Knowledge and attitudes towards genetic testing in those affected with Parkinson’s disease - Tracey M Scuffham; Aideen McInerny-Leo; Shu-Kay Ng; George Mellick (Journal of Community Genetics, 2014)

Novel molecular determinants of viral susceptibility and resistance in the lipidome of E miliania huxleyi - James M. Fulton; Helen F. Fredricks; Kay D. Bidle; Assaf Vardi; B. Jacob Kendrick; Giacomo R. DiTullio; Benjamin A. S. Van Mooy (Environmental Microbiology, 2014)
Summary Viruses play a key role in controlling the population dynamics of algae, including E miliania huxleyi , a globally distributed haptophyte with calcite coccoliths that comprise ca. 50% of the sinking carbonate flux from the surface ocean. E miliania huxleyi viruses ( EhVs ) routinely infect and terminate E . huxleyi blooms. EhVs are surrounded by a lipid envelope, which we found to be comprised largely of glycosphingolipids ( GSLs ) with lesser amounts of polar glycerolipids. Infection appears to involve membrane fusion between the virus and host, and we hypothesized that specific polar lipids may facilitate virus attachment. We identified three novel intact polar lipids in E . huxleyi strain CCMP 374 and EhV 86, including a GSL with a monosaccharide sialic acid headgroup ( sGSL ); for all 11 E . huxleyi strains we tested, there was a direct relationship between sGSL content and sensitivity to infection by EhV 1, EhV 86 and EhV 163. In mesocosms, the E . huxleyi population with greatest initial sGSL content had the highest rate of virus‐induced mortality. We propose potential physiological roles for sGSL that would be beneficial for growth but leave cells susceptible to infection, thus furthering the discussion of R ed Q ueen‐based co‐evolution and the cost(s) of sensitivity and resistance in the dynamic E . huxleyi ‐ EhV system.

Isolation and characterization of lipid rafts in E miliania huxleyi : a role for membrane microdomains in host–virus interactions - Suzanne L. Rose; James M. Fulton; Christopher M. Brown; Frank Natale; Benjamin A. S. Van Mooy; Kay D. Bidle (Environmental Microbiology, 2014)
Summary Coccolithoviruses employ a suite of glycosphingolipids ( GSLs ) to successfully infect the globally important coccolithophore E miliania huxleyi . Lipid rafts, chemically distinct membrane lipid microdomains that are enriched in GSLs and are involved in sensing extracellular stimuli and activating signalling cascades through protein–protein interactions, likely play a fundamental role in host–virus interactions. Using combined lipidomics, proteomics and bioinformatics, we isolated and characterized the lipid and protein content of lipid rafts from control E . huxleyi cells and those infected with EhV 86, the type strain for C occolithovirus . Lipid raft‐enriched fractions were isolated and purified as buoyant, detergent‐resistant membranes ( DRMs ) in OptiPrep density gradients. Transmission electron microscopy of vesicle morphology, polymerase chain reaction amplification of the EhV major capsid protein gene and immunoreactivity to flotillin antisera served as respective physical, molecular and biochemical markers. Subsequent lipid characterization of DRMs via high performance liquid chromatography‐triple quadrapole mass spectrometry revealed four distinct GSL classes. Parallel proteomic analysis confirmed flotillin as a major lipid raft protein, along with a variety of proteins affiliated with host defence, programmed cell death and innate immunity pathways. The detection of an EhV 86‐encoded C ‐type lectin‐containing protein confirmed that infection occurs at the interface between lipid rafts and cellular stress/death pathways via specific GSLs and raft‐associated proteins.

Developing Marine Protected Area Networks in the Coral Triangle: Good Practices for Expanding the Coral Triangle Marine Protected Area System - Rebecca Weeks; Porfirio M. Aliño; Scott Atkinson; Pacifico Beldia; Augustine Binson; Wilfredo L. Campos; Rili Djohani; Alison L. Green; Richard Hamilton; Vera Horigue; Robecca Jumin; Kay Kalim; et al. (Coastal Management, 2014)

Quantitative Genetics of Response to Novelty and Other Stimuli by Infant Rhesus Macaques (Macaca mulatta) Across Three Behavioral Assessments - G. L. Fawcett; A. M. Dettmer; D. Kay; M. Raveendran; J. D. Higley; N. D. Ryan; J. L. Cameron; J. Rogers (International Journal of Primatology, 2014)

Hindbrain orexin 1 receptors influence palatable food intake, operant responding for food, and food-conditioned place preference in rats - Kristen Kay; Eric M. Parise; Nicole Lilly; Diana L. Williams (Psychopharmacology, 2014)

Seasonal reliance on nectar by an insectivorous bat revealed by stable isotopes - Winifred F. Frick; J. Ryan Shipley; Jeffrey F. Kelly; Paul A. Heady; Kathleen M. Kay (Oecologia, 2014)

The social, economic, and environmental contributions of Pan African Sanctuary Alliance primate sanctuaries in Africa - Gina M. Ferrie; Kay H. Farmer; Chris W. Kuhar; Alison P. Grand; Julie Sherman; Tammie L. Bettinger (Biodiversity and Conservation, 2014)

Multivariate analysis of MLH1 c.1664T>C (p.Leu555Pro) mismatch repair gene variant demonstrates its pathogenicity - M. P. Farrell; D. J. Hughes; M. Drost; A. J. Wallace; R. J. Cummins; T. A. Fletcher; M. A. Meany; E. W. Kay; N. de Wind; D. G. Power; E. J. Andrews; A. J. Green; et al. (Familial Cancer, 2013)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Lifestyle, dietary factors, and antibody levels to oral bacteria in cancer-free participants of a European cohort study - Dominique S. Michaud; Jacques Izard; Zachary Rubin; Ingegerd Johansson; Elisabete Weiderpass; Anne Tjønneland; Anja Olsen; Kim Overvad; Marie Christine Boutron-Ruault; Françoise Clavel-Chapelon; Laure Dossus; Rudolf Kaaks; et al. (Cancer Causes & Control, 2013)

Multicolour flow cytometry analyses and autofluorescence in chlorophytes: lessons from programmed cell death studies in Chlamydomonas reinhardtii - Patti Kay; Rajdeep Choudhury; Marietha Nel; Monica V. Orellana; Pierre M. Durand (Journal of Applied Phycology, 2013)

Biology and host range of Omolabus piceus, a weevil rejected for biological control for Schinus terebinthifolius in the USA - G. S. Wheeler; F. Mc Kay; M. D. Vitorino; D. A. Williams (BioControl, 2013)

Restricted gene flow within and between rapidly diverging Neotropical plant species - Yann Surget‐Groba; Kathleen M. Kay (Molecular Ecology, 2013)
Speciation involves the evolution of traits and genetic differences that contribute to reproductive isolation and the cessation of gene flow, and studying closely related species and divergent populations gives insight into how these phenomena proceed. Here, we document patterns of gene flow within and between two members of a rapid Neotropical species radiation, C ostus pulverulentus and C ostus scaber ( C ostaceae). These species co‐occur in the tropical rainforest and share pollinators, but are reproductively isolated by a series of prezygotic barriers, some of which show evidence of reinforcement at sympatric sites. Here, we genotype microsatellite markers in plants from eight sites that span the geographical range of both species, including four sympatric sites. We also genotype putative hybrids found at two sympatric sites. We find high levels of genetic isolation among populations within each species and low but detectable levels of introgression between species at sympatric sites. Putative hybrids identified by morphology are consistent with F 1 or more advanced hybrids. Our results highlight the effectiveness of prezygotic isolating mechanisms at maintaining species boundaries in young radiations and provide empirical data on levels of gene flow consistent with reinforcement.

Drought alters the expression of mating system traits in two species of Clarkia - Kathleen M. Kay; Devon A. Picklum (Evolutionary Ecology, 2013)

Characterization of water and wildlife strains as a subgroup of C ampylobacter jejuni using DNA microarrays - Richard A. Stabler; Jonas T. Larsson; Suaad Al‐Jaberi; Eva M. Nielsen; Emily Kay; Clarence C. Tam; Craig D. Higgins; Laura C. Rodrigues; Judith F. Richardson; Sarah J. O'Brien; Brendan W. Wren (Environmental Microbiology, 2013)
Summary C ampylobacter jejuni is the leading cause of human bacterial gastroenteritis worldwide, but source attribution of the organism is difficult. Previously, DNA microarrays were used to investigate isolate source, which suggested a non‐livestock source of infection. In this study we analysed the genome content of 162 clinical, livestock and water and wildlife ( WW ) associated isolates combined with the previous study. Isolates were grouped by genotypes into nine clusters ( C 1 to C 9). Multilocus sequence typing ( MLST ) data demonstrated that livestock associated clonal complexes dominated clusters C 1– C 6. The majority of WW isolates were present in the C 9 cluster. Analysis of previously reported genomic variable regions demonstrated that these regions were linked to specific clusters. Two novel variable regions were identified. A six gene multiplex PCR ( mPCR ) assay, designed to effectively differentiated strains into clusters, was validated with 30 isolates. A further five WW isolates were tested by m PCR and were assigned to the C 7‐ C 9 group of clusters. The predictive mPCR test could be used to indicate if a clinical case has come from domesticated or WW sources. Our findings provide further evidence that WW C . jejuni subtypes show niche adaptation and may be important in causing human infection.

The impact of culture medium on the development and physiology of biofilms of Pseudomonas fluorescens formed on polyurethane paint - Wendy J. Crookes-Goodson; Caitlin L. Bojanowski; Michelle L. Kay; Pamela F. Lloyd; Andrew Blankemeier; Jennifer M. Hurtubise; Kristi M. Singh; Daniel E. Barlow; Harold D. Ladouceur; D. Matt Eby; Glenn R. Johnson; Peter A. Mirau; et al. (Biofouling, 2013)

No evidence for cumulative effects in a Dnmt3b hypomorph across multiple generations - Neil A. Youngson; Trevor Epp; Amity R. Roberts; Lucia Daxinger; Alyson Ashe; Edward Huang; Krystal L. Lester; Sarah K. Harten; Graham F. Kay; Timothy Cox; Jacqueline M. Matthews; Suyinn Chong; et al. (Mammalian Genome, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Effects of mu opioid receptor antagonism on cognition in obese binge-eating individuals - Samuel R. Chamberlain; Karin Mogg; Brendan P. Bradley; Annelize Koch; Chris M. Dodds; Wenli X. Tao; Kay Maltby; Bhopinder Sarai; Antonella Napolitano; Duncan B. Richards; Edward T. Bullmore; Pradeep J. Nathan (Psychopharmacology, 2012)

Properties of blebbistatin for cardiac optical mapping and other imaging applications - Luther M. Swift; Huda Asfour; Nikki G. Posnack; Ara Arutunyan; Matthew W. Kay; Narine Sarvazyan (Pflügers Archiv - European Journal of Physiology, 2012)

Nprl3 is required for normal development of the cardiovascular system - Monika S. Kowalczyk; Jim R. Hughes; Christian Babbs; Luis Sanchez-Pulido; Dorota Szumska; Jacqueline A. Sharpe; Jacqueline A. Sloane-Stanley; Gillian M. Morriss-Kay; Leslie B. Smoot; Amy E. Roberts; Hugh Watkins; Shoumo Bhattacharya; et al. (Mammalian Genome, 2012)

Oncologists’ Confidence in Knowledge of Fertility Issues for Young Women with Cancer - Christine Duffy; Susan M. Allen; Catherine Dube; Kay Dickersin (Journal of Cancer Education, 2012)

Folate and vitamin B12-related genes and risk for omphalocele - James L. Mills; Tonia C. Carter; Denise M. Kay; Marilyn L. Browne; Lawrence C. Brody; Aiyi Liu; Paul A. Romitti; Michele Caggana; Charlotte M. Druschel (Human Genetics, 2012)

Reproductive success of three passerine species exposed to dioxin-like compounds near Midland, Michigan, USA - Timothy B. Fredricks; Matthew J. Zwiernik; Rita M. Seston; Sarah J. Coefield; Cassandra N. Glaspie; Dustin L. Tazelaar; Denise P. Kay; John L. Newsted; John P. Giesy (Ecotoxicology, 2012)

Development of regional future climate change scenarios in South America using the Eta CPTEC/HadCM3 climate change projections: climatology and regional analyses for the Amazon, São Francisco and the Paraná River basins - Jose A. Marengo; Sin Chan Chou; Gillian Kay; Lincoln M. Alves; José F. Pesquero; Wagner R. Soares; Daniel C. Santos; André A. Lyra; Gustavo Sueiro; Richard Betts; Diego J. Chagas; Jorge L. Gomes; et al. (Climate Dynamics, 2012)

The Arctic’s rapidly shrinking sea ice cover: a research synthesis - Julienne C. Stroeve; Mark C. Serreze; Marika M. Holland; Jennifer E. Kay; James Malanik; Andrew P. Barrett (Climatic Change, 2012)

Downscaling of South America present climate driven by 4-member HadCM3 runs - Sin Chan Chou; José A. Marengo; André A. Lyra; Gustavo Sueiro; José F. Pesquero; Lincoln M. Alves; Gillian Kay; Richard Betts; Diego J. Chagas; Jorge L. Gomes; Josiane F. Bustamante; Priscila Tavares (Climate Dynamics, 2012)

Analysis of incurred crystal violet in Atlantic salmon ( Salmo salar L.): comparison between the analysis of crystal violet as an individual parent and leucocrystal violet and as total crystal violet after oxidation with 2,3-dichloro-5,6-dicyanobenzoquinone - D. Chan; J.A. Tarbin; G. Stubbings; J. Kay; M. Sharman (Food Additives & Contaminants: Part A, 2012)

Effect of simulated dives on diastolic function in healthy men - Jochen Hansel; Kay Tetzlaff; Detlef Axmann; Andreas M. Niess; Christof Burgstahler (European Journal of Applied Physiology, 2012)

Erratum to: Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2011)

Menopausal hormone therapy and risk of ovarian cancer in the European prospective investigation into cancer and nutrition - Konstantinos K. Tsilidis; Naomi E. Allen; Timothy J. Key; Laure Dossus; Rudolf Kaaks; Kjersti Bakken; Eiliv Lund; Agnès Fournier; Christina C. Dahm; Kim Overvad; Louise Hansen; Anne Tjønneland; et al. (Cancer Causes & Control, 2011)

Enzymatic Characterisation of USP7 Deubiquitinating activity and Inhibition - Jonathan D. Wrigley; Kay Eckersley; Ian M. Hardern; Lindsey Millard; Michael Walters; Stephen W. Peters; Richard Mott; Thorsten Nowak; Richard A. Ward; Peter B. Simpson; Kevin Hudson (Cell Biochemistry and Biophysics, 2011)

Consumption of meat and fish and risk of lung cancer: results from the European Prospective Investigation into Cancer and Nutrition - Jakob Linseisen; Sabine Rohrmann; Bas Bueno-de-Mesquita; Frederike L. Büchner; Hendriek C. Boshuizen; Antonio Agudo; Inger Torhild Gram; Christina C. Dahm; Kim Overvad; Rikke Egeberg; Anne Tjønneland; Heiner Boeing; et al. (Cancer Causes & Control, 2011)

A kinetic analysis of three modified novel nitroreductases - Christopher D. Gwenin; Maher Kalaji; Peter A. Williams; Catherine M. Kay (Biodegradation, 2011)

Estrogen-induced effects on the neuro-mechanics of hopping in humans - Adam L. Bryant; Kay M. Crossley; Simon Bartold; Erik Hohmann; Ross A. Clark (European Journal of Applied Physiology, 2011)

The geochemistry of a dying continental arc: the Incapillo Caldera and Dome Complex of the southernmost Central Andean Volcanic Zone (~28°S) - A. R. Goss; S. M. Kay; C. Mpodozis (Contributions to Mineralogy and Petrology, 2011)

Dating problems with selected mining lakes and the adjacent groundwater body in Lusatia, Germany - Anne Seebach; Christoph von Rohden; Johann Ilmberger; Stephan M. Weise; Kay Knöller (Isotopes in Environmental and Health Studies, 2010)

Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2010)

Prospective study of physical activity and risk of primary adenocarcinomas of the oesophagus and stomach in the EPIC (European Prospective Investigation into Cancer and nutrition) cohort - José María Huerta; Carmen Navarro; María-Dolores Chirlaque; María-José Tormo; Karen Steindorf; Genevieve Buckland; Fátima Carneiro; Nina Føns Johnsen; Kim Overvad; Jakob Stegger; Anne Tjønneland; Marie-Christine Boutron-Ruault; et al. (Cancer Causes & Control, 2010)

Passerine Exposure to Primarily PCDFs and PCDDs in the River Floodplains Near Midland, Michigan, USA - Timothy B. Fredricks; Matthew J. Zwiernik; Rita M. Seston; Sarah J. Coefield; Stephanie C. Plautz; Dustin L. Tazelaar; Melissa S. Shotwell; Patrick W. Bradley; Denise P. Kay; John P. Giesy (Archives of Environmental Contamination and Toxicology, 2010)

Lifestyle factors and serum androgens among 636 middle aged men from seven countries in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Reiko Suzuki; Naomi E. Allen; Paul N. Appleby; Timothy J. Key; Laure Dossus; Anne Tjønneland; Nina Føns Johnsen; Kim Overvad; Carlotta Sacerdote; Domenico Palli; Vittorio Krogh; Rosario Tumino; et al. (Cancer Causes & Control, 2009)

Lifestyle factors and serum androgens among 636 middle aged men from seven countries in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Reiko Suzuki; Naomi E. Allen; Paul N. Appleby; Timothy J. Key; Laure Dossus; Anne Tjønneland; Nina Føns Johnsen; Kim Overvad; Carlotta Sacerdote; Domenico Palli; Vittorio Krogh; Rosario Tumino; et al. (Cancer Causes & Control, 2009)

Ethanol intake and the risk of pancreatic cancer in the European prospective investigation into cancer and nutrition (EPIC) - Sabine Rohrmann; Jakob Linseisen; Alina Vrieling; Paolo Boffetta; Rachael Z. Stolzenberg-Solomon; Albert B. Lowenfels; Majken K. Jensen; Kim Overvad; Anja Olsen; Anne Tjonneland; Marie-Christine Boutron-Ruault; Francoise Clavel-Chapelon; et al. (Cancer Causes & Control, 2009)

Quinoprotein ethanol dehydrogenase from Pseudomonas aeruginosa: the unusual disulfide ring formed by adjacent cysteine residues is essential for efficient electron transfer to cytochrome c 550 - Bina Mennenga; Christopher W. M. Kay; Helmut Görisch (Archives of Microbiology, 2009)

Hypoxia and cardiac arrhythmias in breath-hold divers during voluntary immersed breath-holds - Jochen Hansel; Isabelle Solleder; Wilfried Gfroerer; Claus M. Muth; Klaus Paulat; Perikles Simon; Hans-C. Heitkamp; Andreas Niess; Kay Tetzlaff (European Journal of Applied Physiology, 2009)

Olfactory system gamma oscillations: the physiological dissection of a cognitive neural system - Daniel Rojas-Líbano; Leslie M. Kay (Cognitive Neurodynamics, 2008)

Contrasting levels of genetic differentiation among putative neutral microsatellite loci in Atlantic herring Clupea harengus populations and the implications for assessing stock structure - Phillip C. Watts; David O’Leary; Mary C. Cross; Jamie Coughlan; Eileen Dillane; Suzanne M. Kay; Suzanne Wylde; René Stet; Richard D. M. Nash; Emma M. C. Hatfield; Thomas F. Cross (Hydrobiologia, 2008)

Characteristics of the respiratory mechanical and muscle function of competitive breath-hold divers - Kay Tetzlaff; Tobias Scholz; Stephan Walterspacher; Claus M. Muth; Jule Metzger; Kai Roecker; Stephan Sorichter (European Journal of Applied Physiology, 2008)

Congo red inhibition as a convenient diagnostic for Flavobacterium psychrophilum - E M Crump; W W Kay (Journal of Fish Diseases, 2008)

Developing UK farmers' institutional capacity to defend their water rights and effectively manage limited water resources - W. Leathes; J. W. Knox; M. G. Kay; P. Trawick; J. A. Rodriguez‐Diaz (Irrigation and Drainage, 2008)
Developing farmers' institutional capacity to defend their water rights is central to sustaining irrigation farming in the UK. Increasing demand and competition for water and the introduction of new water regulations have led many farmers to re‐evaluate the security of their water rights. As a consequence, some have formed water abstractors groups, a trend which is strongest in eastern England, where irrigation is most concentrated and water resources are most stressed. “Collective choice” theory attempts to explain how institutions evolve to share common resources and what key elements are needed for them to endure over the long term. This paper compares the characteristics of four existing water abstractors groups against those of “collective choice” theory. It concludes that it is applicable in the UK context and relevant when addressing a range of emerging water management challenges. The approach taken offers a means of analysing capacity at an institutional level and suggests a way of supporting the development of existing water abstractors groups as well as developing new ones. It is argued that this approach to developing institutional capacity could be used elsewhere where problems between resource availability, environmental protection and the sustainability of agricultural production are evident. Copyright © 2008 John Wiley & Sons, Ltd.

Exploring gene-environment interactions in Parkinson’s disease - Colin C. McCulloch; Denise M. Kay; Stewart A. Factor; Ali Samii; John G. Nutt; Donald S. Higgins; Alida Griffith; John W. Roberts; Berta C. Leis; Jennifer S. Montimurro; Cyrus P. Zabetian; Haydeh Payami (Human Genetics, 2008)

Glycomic mapping of O- and N-linked glycans from major rat sublingual mucin - Shin-Yi Yu; Kay-Hooi Khoo; Zhangung Yang; Anthony Herp; Albert M. Wu (Glycoconjugate Journal, 2008)

Physical and chemical limnology of alpine lakes and pools in the Rwenzori Mountains (Uganda–DR Congo) - Hilde Eggermont; James M. Russell; Georg Schettler; Kay Van Damme; Ilse Bessems; Dirk Verschuren (Hydrobiologia, 2007)

Factors affecting river health and its assessment over broad geographic ranges: The Western Australian experience - S. A. Halse; M. D. Scanlon; J. S. Cocking; M. J. Smith; W. R. Kay (Environmental Monitoring and Assessment, 2007)

Fruit and vegetable consumption and lymphoma risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Sabine Rohrmann; Nikolaus Becker; Jakob Linseisen; Alexandra Nieters; Thomas Rüdiger; Ole Raaschou-Nielsen; Anne Tjønneland; Hans E. Johnsen; Kim Overvad; Rudolf Kaaks; Manuela M. Bergmann; Heiner Boeing; et al. (Cancer Causes & Control, 2007)

Alcohol intake and breast cancer risk: the European Prospective Investigation into Cancer and Nutrition (EPIC) - Anne Tjønneland; Jane Christensen; Anja Olsen; Connie Stripp; Birthe L. Thomsen; Kim Overvad; Petra H. M. Peeters; Carla H. van Gils; H. Bas Bueno-de-Mesquita; Marga C. Ocké; Anne Thiebaut; Agnès Fournier; et al. (Cancer Causes & Control, 2007)

Anthropometric factors and risk of endometrial cancer: the European prospective investigation into cancer and nutrition - Christine Friedenreich; Anne Cust; Petra H. Lahmann; Karen Steindorf; Marie-Christine Boutron-Ruault; Françoise Clavel-Chapelon; Sylvie Mesrine; Jakob Linseisen; Sabine Rohrmann; Heiner Boeing; Tobias Pischon; Anne Tjønneland; et al. (Cancer Causes & Control, 2007)

Stoichiometric response of nitrogen-fixing and non-fixing dicots to manipulations of CO2, nitrogen, and diversity - Amy M. Novotny; John D. Schade; Sarah E. Hobbie; Adam D. Kay; Marcia Kyle; Peter B. Reich; James J. Elser (Oecologia, 2007)

Tools for health: the efficacy of a tailored intervention targeted for construction laborers - Glorian Sorensen; Elizabeth M. Barbeau; Anne M. Stoddard; Mary Kay Hunt; Roberta Goldman; Ann Smith; Angela A. Brennan; Lorraine Wallace (Cancer Causes & Control, 2007)

Behavioral Adaptation of Pan troglodytes troglodytes - Kay H. Farmer; Hannah M. Buchanan-Smith; Aliette Jamart (International Journal of Primatology, 2006)

Behavioral Adaptation of Pan troglodytes troglodytes - Kay H. Farmer; Hannah M. Buchanan-Smith; Aliette Jamart (International Journal of Primatology, 2006)

Reducing Cigarette Smoking Among Working Adolescents: Results from the SMART Study - Anne M. Stoddard; Pebbles Fagan; Glorian Sorensen; Mary Kay Hunt; Lindsay Frazier; Kathy Girod (Cancer Causes & Control, 2005)

C-peptide, IGF-I, sex-steroid hormones and adiposity: a cross-sectional study in healthy women within the European Prospective Investigation into Cancer and Nutrition (EPIC) - Irene D. Bezemer; Sabina Rinaldi; Laure Dossus; Carla H. van. Gils; Petra H. M. Peeters; Paulus A. H. van. Noord; H. Bas Bueno-de-Mesquita; Soren Paaske Johnsen; Kim Overvad; Anja Olsen; Anne Tjønneland; Heiner Boeing; et al. (Cancer Causes & Control, 2005)

Root response to Fusarium solani f. sp . glycines: temporal accumulation of transcripts in partially resistant and susceptible soybean - M. J. Iqbal; Satsuki Yaegashi; Rubina Ahsan; Kay L. Shopinski; David A. Lightfoot (Theoretical and Applied Genetics, 2005)

Towards a mutant map of the mouse ? new models of neurological, behavioural, deafness, bone, renal and blood disorders - Sohaila Rastan; Tertius Hough; Amy Kierman; Rachel Hardisty; Alexandra Erven; Ian C. Gray; Stepanie Voeling; Adrian Isaacs; Hsun Tsai; Mark Strivens; Rebecca Washbourne; Claire Thornton; et al. (Genetica, 2004)

Extracting Wave Structure from Biological Data with Application to Responses in Turtle Visual Cortex - Kay A. Robbins; David M. Senseman (Journal of Computational Neuroscience, 2004)

Behavioural structuring of relatedness in the spotted hyena ( Crocuta crocuta ) suggests direct fitness benefits of clan‐level cooperation - Russell C. Van Horn; Anne L. Engh; Kim T. Scribner; Stephan M. Funk; Kay E. Holekamp (Molecular Ecology, 2004)
Spotted hyenas ( Crocuta crocuta ) are gregarious carnivores that live in multigenerational social groups, called clans, containing one to several matrilines. Members of multiple matrilines within a clan cooperate during dangerous interactions with inter‐ and intraspecific competitors. The evolution of cooperation may be influenced by relatedness between individuals, which in turn is influenced by reproductive skew and mate choice, dispersal and territorial behaviours. Behavioural data exist for spotted hyenas, but corresponding data on patterns of relatedness are unavailable; this lack of data makes it difficult to assess the relative importance of selection pressures favouring cooperative behaviour within and among groups. Therefore we conducted a longitudinal analysis of relatedness within a single large clan of spotted hyenas, as well as a cross‐sectional analysis of relatedness among hyenas from multiple clans. Within a clan, patterns of relatedness reflected known pedigree relationships, and relatedness was higher within than among matrilines, even across generations. Although mean within‐matriline relatedness varied among matrilines, it did not decline with matriline rank. On average, clan members were not related closely, due to high levels of male‐mediated gene flow among clans, and relatedness declined very slightly across clan borders. Low mean relatedness within clans suggests that spotted hyenas cooperate with unrelated clan‐mates against close paternal kin in other clans. Our data also suggest that spotted hyenas must derive large net direct fitness benefits from group living and cooperation.

Functional coupling as a basic mechanism of feedback regulation of cardiac energy metabolism - V.A. Saks; A.V. Kuznetsov; M. Vendelin; K. Guerrero; L. Kay; E.K. Seppet (Molecular and Cellular Biochemistry, 2004)

Recruitment in the intertidal limpet Lottia digitalis (Patellogastropoda: Lottiidae) may be driven by settlement cues associated with adult habitat - Kay M. (Marine Biology, 2002)

A comprehensive worksite cancer prevention intervention: behavior change results from a randomized controlled trial (United States) - Glorian Sorensen; Anne M Stoddard; Anthony D. LaMontagne; Karen Emmons; Mary Kay Hunt; Richard Youngstrom; Deborah McLellan; David C Christiani (Cancer Causes & Control, 2002)

Spatial distribution, size structure, and prey of Craspedacusta sowerbyi Lankester in a shallow New Zealand lake - Ian K.G. Boothroyd; M. Kay Etheredge; John D. Green (Hydrobiologia, 2002)

Contractile function of rat myocardium is less susceptible to hypoxia/reoxygenation after acute infarction - Kay-Dietrich Wagner; Gunnar Gmehling; Joachim Günther; Harald M. Stauss; Karsten Mydlak; Heinz Theres; Holger Scholz; Ingolf Schimke (Molecular and Cellular Biochemistry, 2001)

Assessment of Ventricular Contractility During Cardiac Magnetic Resonance Imaging Examinations Using Normalized Maximal Ventricular Power - Randy M. Setser; Kay Sayre; Sebastian Flacke; Jon Chia; Kamilla Lunn; Christine H. Lorenz (Annals of Biomedical Engineering, 2001)

Carbonatite metasomatized peridotite xenoliths from southern Patagonia: implications for lithospheric processes and Neogene plateau magmatism - Matthew L. Gorring; Suzanne M. Kay (Contributions to Mineralogy and Petrology, 2000)

Exchangeable ammonium and nitrate from different nitrogen fertilizer preparations in polyacrylamide-treated and untreated agricultural soils - J. L. Kay-Shoemake; M. E. Watwood; L. Kilpatrick; K. Harris (Biology and Fertility of Soils, 2000)

Effects of Measurement Error and Sampling Resolution on Estimates of Atrial Tissue Recovery Parameters - M. W. Kay; P. V. Bayly; R. B. Schuessler (Annals of Biomedical Engineering, 2000)

Soil amidase activity in polyacrylamide-treated soils and potential activity toward common amide-containing pesticides - Jeanine L. Kay-Shoemake; M. E. Watwood; Robert E. Sojka; Roderick D. Lentz (Biology and Fertility of Soils, 2000)

Apoptotic cell death and related gene expression in metastatic tumors of AKR lymphomas of varying malignancy - S. Kay; M. Michowitz; N. Donin; D. Katzenelson; A. Siegal; J. Sinai; J. Ravia; A. Pinchassov; J. Leibovici (Apoptosis, 1999)

Anti-T cell strategies in asthma - O. M. Kon; A. B. Kay (Inflammation Research, 1999)

The relationship between the rate of starch synthesis, the adenosine 5′-diphosphoglucose concentration and the amylose content of starch in developing pea embryos - Belinda R. Clarke; Kay Denyer; Colin F. Jenner; Alison M. Smith (Planta, 1999)

Microdialysis Evaluation of the Ocular Pharmacokinetics of Propranolol in the Conscious Rabbit - Kay D. Rittenhouse; Robert L. Peiffer; Gary M. Pollack (Pharmaceutical Research, 1999)

Genomic organization and refined mapping of the mouse β-dystrobrevin gene - Nellie Y. Loh; Helen J. Ambrose; Lisa M. Guay-Woodford; Srimita DasGupta; Ralph A. Nawrotzki; Derek J. Blake; Kay E. Davies (Mammalian Genome, 1998)

Angiogenesis induced by tumor necrosis factor-agr; is mediated by α4 integrins - Peter Vanderslice; Christy L. Munsch; Eugene Rachal; David Erichsen; Kay M. Sughrue; Ann N. Truong; James N. Wygant; Bradley W. McIntyre; Suzanne G. Eskin; Ronald G. Tilton; Peter J. Polverini (Angiogenesis, 1998)

The amelioration of aluminium toxicity by silicon in wheat ( Triticum aestivum L.): malate exudation as evidence for an in planta mechanism - Kay M. Cocker; David E. Evans; Martin J. Hodson (Planta, 1998)

Isolation and analysis of a gene bbe1 encoding the berberine bridge enzyme from the California poppy Eschscholzia californica - Kay Hauschild; Hubert H. Pauli; Toni M. Kutchan (Plant Molecular Biology, 1998)

Apoptosis, cell proliferation and in vivo biological behaviour of primary and metastatic tumour cells of an AKR lymphoma variant - N. Donin; D. Katzenelson; J. Ravia; J. Hiss; G. Schiby; S. Kay; J. Sinai; M. Michowitz; J. Leibovici (Apoptosis, 1997)

Nutrient concentration relationships between the fourth petiole and upper-stem of potato plants - D. T. Westermann; S. M. Bosma; M. A. Kay (American Journal of Potato Research, 1994)

Isolation and characterization of dengue viruses serotype 1 from an epidemic in northern Queensland, Australia - J. Blok; B. H. Kay; R. A. Hall; B. M. Gorman (Archives of Virology, 1988)

Molecular weight and quaternary structure of ribulose bisphosphate carboxylase from the cyanobacterium, Synechococcus sp. - T. John Andrews; Kay M. Abel; Diedrik Menzel; Murray R. Badger (Archives of Microbiology, 1981)